Nanostructured molded article
Multilayer nanostructures with InP cores and ZnSe/ZnS shells, fabricated using high-temperature synthesis, overcome the stability and toxicity issues of existing quantum dots, achieving long-lasting high photoluminescence without harmful materials.
Patent Information
- Application Number
- JP2024229795
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2017-10-25
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-10
AI Technical Summary
Existing highly luminescent nanostructures, particularly quantum dots, face challenges in maintaining high photoluminescence strength over time due to instability and the use of toxic materials like cadmium, mercury, or lead, which are environmentally harmful and prohibited by regulations.
The development of multilayer nanostructures comprising a core and at least two shells, where the shells comprise different materials, specifically InP cores with ZnSe and ZnS shells, and the shells have a thickness between 0.7 nm and 3.5 nm, enhancing stability and photoluminescence. This method avoids the use of toxic materials and employs high-temperature synthesis for improved shell growth.
The proposed nanostructures exhibit high stability and maintain strong photoluminescence over a long period, while being environmentally friendly and free from toxic materials, thus addressing the limitations of existing technologies.
Smart Images

Figure 2025060870000001_ABST
Abstract
Description
[Technical field]
[0001] Highly luminescent nanostructures, particularly highly luminescent quantum dots, are provided that include a nanocrystalline core and thick shells of ZnSe and ZnS. These nanostructures include one or more ZnSe shells with a gradient between the ZnSe and ZnS shells. x S 1-x The nanostructure may have a monolayer, where the value of x gradually decreases from the interior to the exterior of the nanostructure. Methods for producing nanostructures are also provided, including high temperature synthesis methods. The thick shell nanostructures of the present invention exhibit high stability and can maintain high levels of photoluminescence intensity over extended periods of time. Nanostructures with increased blue light absorption are also provided. [Background technology]
[0002]
[0002] Semiconductor nanostructures can be incorporated into various electronic and optical devices. The electrical and optical properties of such nanostructures vary, for example, depending on their composition, shape, and size. For example, the size-tunable nature of semiconductor nanoparticles is of great interest for applications such as light-emitting diodes (LEDs), lasers, and biomedical labels. Highly luminescent nanostructures are particularly desirable for such applications.
[0003]
[0003] To fully utilize the potential of nanostructures in applications such as LEDs and displays, nanostructures must simultaneously meet five criteria: narrow and symmetric emission spectrum, high photoluminescence (PL) quantum yield (QY), high optical stability, environmentally friendly materials, and low-cost mass production methods. Most previous research on highly luminescent and color-tunable quantum dots has focused on materials containing cadmium, mercury, or lead. Wang, A., et al., Nanoscale 7:2951-2959 (2015). However, there is growing concern that toxic materials such as cadmium, mercury, or lead pose serious threats to human health and the environment, and the European Union's Restriction of Hazardous Substances rules prohibit consumer electronics containing these materials in more than trace amounts. Therefore, there is a need for the production of cadmium-, mercury-, and lead-free materials for manufacturing LEDs and displays.
[0004]
[0004] Cadmium-free quantum dots based on indium phosphide are inherently less stable than the prototypic cadmium selenide quantum dots: the higher valence and conduction band energy levels make InP quantum dots more susceptible to photooxidation via electron transfer from excited quantum dots to oxygen and to photoluminescence quenching by electron donating agents such as amines or thiols that can refill the hole states of excited quantum dots, thus suppressing the radiative recombination of excitons. See, e.g., Chibli, H., et al., "Cytotoxicity of InP / ZnS quantum dots related to reactive oxygen species generation," Nanoscale 3:2552-2559 (2011); Blackburn, JL, et al., "Electron and Hole Transfer from Indium Phosphide Quantum Dots," J. Phys. Chem. B 109:2625-2631 (2005); and Selmarten, D., et al., "Quenching of Semiconductor Quantum Dot Photoluminescence by a π-Conjugated Polymer," J. Phys. Chem. B 109:15927-15933 (2005).
[0005]
[0005] Inorganic shell coating on quantum dots is one of the common methods to tailor their electronic structure. Moreover, depositing an inorganic shell can form more robust particles by passivating surface defects. Ziegler, J., et al., Adv. Mater. 20:4068-4073 (2008). For example, a shell of a wider band gap semiconductor material, such as ZnS, can be deposited on a core with a narrower band gap, such as CdSe or InP, resulting in a structure in which excitons are confined within the core. This method increases the probability of radiative recombination, allowing the synthesis of highly efficient quantum dots with thin shell coatings with quantum yields close to unity.
[0006]
[0006] Core-shell quantum dots, which have a shell of wider bandgap semiconductor material deposited on a core with a narrower bandgap, are still susceptible to degradation mechanisms because a shell thinner than 1 nanometer does not adequately inhibit charge transfer to environmental factors. A thicker shell coating of several nanometers reduces the probability of tunneling or exciton transfer, and thus thicker shell coatings are believed to improve stability, a finding already demonstrated for the CdSe / CdS system.
[0007]
[0007] Regardless of the composition of the quantum dots, most quantum dots do not maintain their inherent high quantum yield after continuous exposure to excitation photons. Precise shell design, such as the formation of multiple shells and thick shells (which causes the carrier wave function in the core to begin to move away from the surface of the quantum dot), has been effective in mitigating the photoinduced degradation of quantum dots. In addition, it has been found that the photodegradation of quantum dots can be delayed by encapsulating them with oxides (physical isolation of the quantum dot surface from their environment). Jo, J.-H., et al., J. Alloys Compd. 647:6-13 (2015).
[0008]
[0008] Thick coatings on CdSe / CdS giant shell quantum dots have been shown to improve their stability against environmental factors and surface charges by separating the emissive core from the surface by several nanometers. There is a need to produce materials that exhibit the improved stability seen with thick shell quantum dots, while also possessing the beneficial properties of thin shell quantum dots, such as high quantum yield, narrow emission peak width, tunable emission wavelength, and colloidal stability.
[0009]
[0009] It is difficult to maintain the beneficial properties of thin-shell quantum dots when thick shells are produced due to a number of disruptions and decomposition possibilities, including: (1) precipitation of dots due to increased mass, reduced surface-to-volume ratio, and increased total surface area; (2) irreversible aggregation of shell material with bridging dots; (3) secondary nucleation of shell material; (4) interfacial defects caused by relaxation of lattice strain; (5) anisotropic shell growth on preferred facets; (6) amorphous shells or non-epitaxial interfaces; and (7) broad emission peaks resulting from broadening the size distribution.
[0010]
[0010] The interfaces of these heterogeneous nanostructures need to be defect-free, because defects act as trapping sites for charge carriers, resulting in both reduced luminescence efficiency and stability. The lattice spacings of these semiconductor materials are inherently different, which creates strain in the crystal lattice at the interface. The energy load of this strain is compensated for by favorable epitaxial arrangement in thin layers, but for thicker layers, the shell material relaxes to its native lattice, forming mismatches and defects at the interface. There is an inherent trade-off between adding more shell material and maintaining the quality of the material. Therefore, it is necessary to find a suitable shell composition that overcomes these problems.
[0011]
[0011] Recent advances have made it possible to obtain highly luminescent simple core nanocrystals. However, the synthesis of these simple core nanocrystals has presented stability and processability problems, which are probably inherent to flat core nanocrystals. Therefore, core / shell nanocrystals are preferred when complex chemical processing of the nanocrystals is required, such as in biomedical applications, or when the nanocrystals require constant excitation, such as in LEDs and lasers. See Li, JJ, et al., J. Am. Chem. Soc. 125:12567-12575 (2003).
[0012]
[0012] There are two important challenges that need to be considered to control the size distribution during the growth of shell materials: (1) eliminating the uniform nucleation of shell materials; and (2) growing a uniform monolayer of shell precursor on all core nanocrystals in solution to form a shell layer of the same thickness around each core nanocrystal. Successive Ionic Layer Adsorption and Reaction (SILAR), originally developed for depositing thin films on solid substrates from a solution bath, has been introduced as a technique for the growth of high-quality core / shell nanocrystals of compound semiconductors.
[0013]
[0013] CdSe / CdS core / shell nanocrystals have been produced with photoluminescence quantum yields of 20-40% using the SILAR method. Li, JJ, et al., J. Am. Chem. Soc. 125:12567-12575 (2003). In the SILAR process, the amount of precursor used for each half-reaction is calculated to give a monolayer coverage of 1 for all cores, a technique that requires accurate information on the surface area of all cores present in the reaction mixture. Furthermore, the SILAR process assumes quantitative reaction yields for both half-reactions, thus accumulating measurement inaccuracies and lack of control after each cycle.
[0014]
[0014] A colloidal atomic layer deposition (c-ALD) process for synthesizing colloidal nanostructures has been proposed in Ithurria, S., et al., J. Am. Chem. Soc. 134:18585-18590 (2012). In the c-ALD process, either nanoparticles or molecular precursors are transferred sequentially between polar and non-polar phases to prevent the accumulation of unreacted precursors and by-products in the reaction mixture. The c-ALD process has been used to grow CdS layers on colloidal CdSe nanocrystals, CdSe nanoplatelets, and CdS nanorods. However, the c-ALD process suffers from the need to use a phase transfer protocol that employs exposure to potentially harmful highly polar solvents such as formamide, N-methyl-formamide, or hydrazine.
[0015]
[0015] It is necessary to find a method for synthesizing thick shells that avoids the possibility of destruction and decomposition of the thick shells. The present invention provides a thick shell coating method that is applicable to the production of cadmium-free quantum dots. Summary of the Invention
[0016]
[0016] The present invention provides a multilayer nanostructure comprising a core and at least two shells, wherein at least two shells comprise different shell materials and at least one shell has a thickness between 0.7 nm and 3.5 nm.
[0017] In some embodiments, the core of the multi-layer nanostructure comprises InP. In some embodiments, at least one shell of the multi-layer nanostructure comprises ZnS. In some embodiments, at least one shell of the multi-layer nanostructure comprises ZnSe.
[0018] In some embodiments, the thickness of at least one shell of the multi-layered nanostructure is between 0.9 nm and 3.5 nm. In some embodiments, the thickness of at least two shells of the multi-layered nanostructure is between 0.7 nm and 3.5 nm.
[0019] In some embodiments, at least one shell of the multi-layered nanostructure comprises ZnS, at least one shell comprises ZnSe, and at least two shells have a thickness between 0.7 nm and 3.5 nm.
[0020] The present invention relates to a method for producing a multi-layer nanostructure, comprising the steps of: (a) contacting a nanocrystalline core with at least two shell precursors; (b) by heating (a) to a temperature between about 200° C. and about 310° C.; A method of manufacturing is provided that includes obtaining a nanostructure comprising at least one shell, the at least one shell comprising between 2.5 and 10 monolayers.
[0021] In some embodiments, the contacted nanocrystalline core comprises InP.
[0022]
[0022] In some embodiments, at least two shell precursors contacted with the nanocrystalline core comprise a zinc source. In some embodiments, the zinc source is selected from the group consisting of zinc oleate, zinc hexanoate, zinc octanoate, zinc laurate, zinc palmitate, zinc stearate, zinc dithiocarbamate, or mixtures thereof. In some embodiments, the zinc source is zinc stearate or zinc oleate.
[0023]
[0023] In some embodiments, the at least two shell precursors contacted with the nanocrystal core comprise a selenium source. In some embodiments, the selenium source is selected from the group consisting of trioctylphosphine selenide, tri(n-butyl)phosphine selenide, tri(sec-butyl)phosphine selenide, tri(tert-butyl)phosphine selenide, trimethylphosphine selenide, triphenylphosphine selenide, diphenylphosphine selenide, phenylphosphine selenide, tricyclohexylphosphine selenide, cyclohexylphosphine selenide, 1-octaneselenol, 1-dodecaneselenol, selenophenol, elemental selenium, bis(trimethylsilyl)selenide, and mixtures thereof. In some embodiments, the selenium source is tri(n-butyl)phosphine selenide or trioctylphosphine selenide.
[0024] In some embodiments, the molar ratio of the core to the selenium source is between 1:2 and 1:1000. In some embodiments, the molar ratio of the core to the selenium source is between 1:10 and 1:1000.
[0025]
[0025] In some embodiments, at least two shell precursors contacted with the nanocrystal core comprise a sulfur source. In some embodiments, the sulfur source is selected from the group consisting of elemental sulfur, octanethiol, dodecanethiol, octadecanethiol, tributylphosphine sulfide, cyclohexyl isothiocyanate, α-toluenethiol, ethylene trithiocarbonate, allyl mercaptan, bis(trimethylsilyl) sulfide, trioctylphosphine sulfide, and mixtures thereof. In some embodiments, the sulfur source is octanethiol.
[0026]
[0026] In some embodiments, the molar ratio of the core to the sulfur source is between 1:2 and 1:1000. In some embodiments, the molar ratio of the core to the sulfur source is between 1:10 and 1:1000.
[0027] In some embodiments, the nanocrystalline core and at least one shell material are heated at a temperature between about 250° C. and about 310° C. In some embodiments, the nanocrystalline core and at least one shell material are heated at a temperature of about 280° C.
[0028] In some embodiments, the heating of the nanocrystalline core and the at least one shell material is maintained for a period of time between 2 minutes and 240 minutes. In some embodiments, the heating of the nanocrystalline core and the at least two shell precursors is maintained for a period of time between 30 minutes and 120 minutes.
[0029] In some embodiments, the contacting of the nanocrystalline core with at least two shell precursors further comprises a solvent. In some embodiments, the solvent is selected from the group consisting of 1-octadecene, 1-hexadecene, 1-eicosene, eicosane, octadecane, hexadecane, tetradecane, squalene, squalane, trioctylphosphine oxide, and dioctyl ether. In some embodiments, the solvent is 1-octadecene.
[0030]
[0030] In some embodiments, the nanocrystal core is an InP nanocrystal, at least one shell comprises ZnS, and at least one shell comprises ZnSe, and heating the nanocrystal core and at least two shell precursors is performed at a temperature between about 250°C and about 310°C.
[0031] The present invention relates to a method for producing a multi-layer nanostructure, comprising the steps of: (a) contacting a nanocrystalline core with at least two shell precursors; (b) heating (a) to a temperature between about 200° C. and about 310° C.; (c) contacting (b) with at least one shell precursor, wherein the at least one shell precursor is different from the shell precursor of (a); (d) by heating (c) to a temperature between about 200° C. and about 310° C.; A method of manufacturing is provided that includes obtaining a nanostructure comprising at least two shells, where at least one shell comprises between 2.5 and 10 monolayers.
[0032]
[0032] In some embodiments, the at least two shell precursors that are contacted include a zinc source. In some embodiments, the zinc source is selected from the group consisting of zinc oleate, zinc hexanoate, zinc octanoate, zinc laurate, zinc palmitate, zinc stearate, zinc dithiocarbamate, or mixtures thereof. In some embodiments, the zinc source is zinc stearate or zinc oleate.
[0033]
[0033] In some embodiments, the at least two shell precursors that are contacted include a selenium source. In some embodiments, the selenium source is selected from the group consisting of trioctylphosphine selenide, tri(n-butyl)phosphine selenide, tri(sec-butyl)phosphine selenide, tri(tert-butyl)phosphine selenide, trimethylphosphine selenide, triphenylphosphine selenide, diphenylphosphine selenide, phenylphosphine selenide, tricyclohexylphosphine selenide, cyclohexylphosphine selenide, 1-octaneselenol, 1-dodecaneselenol, selenophenol, elemental selenium, bis(trimethylsilyl)selenide, and mixtures thereof. In some embodiments, the selenium source is tri(n-butyl)phosphine selenide or trioctylphosphine selenide.
[0034]
[0034] In some embodiments, the at least two shell precursors that are contacted include a sulfur source. In some embodiments, the sulfur source is selected from the group consisting of elemental sulfur, octanethiol, dodecanethiol, octadecanethiol, tributylphosphine sulfide, cyclohexyl isothiocyanate, α-toluenethiol, ethylene trithiocarbonate, allyl mercaptan, bis(trimethylsilyl) sulfide, trioctylphosphine sulfide, and mixtures thereof. In some embodiments, the sulfur source is octanethiol.
[0035]
[0035] The present invention also provides a multilayered nanostructure comprising a core and at least two shells, at least two shells comprising different shell materials, at least one shell comprising between about 2 and about 10 monolayers of shell material, and the nanostructure having a normalized optical density between about 1.0 and about 8.0.
[0036] In some embodiments, the multi-layer nanostructure comprises a core selected from the group consisting of ZnO, ZnSe, ZnS, ZnTe, CdO, CdSe, CdS, CdTe, HgO, HgS, HgTe, BN, BP, BAs, BSb, AlN, AlP, AlAs, AlSb, GaN, GaP, GaSb, InN, InP, InAs, and InSb. In some embodiments, the multi-layer nanostructure comprises a core selected from the group consisting of ZnS, ZnSe, CdSe, CdS, and InP. In some embodiments, the multi-layer nanostructure core comprises InP.
[0037] In some embodiments, the multi-layered nanostructure comprises at least two shells, and at least one shell comprises ZnS.
[0038] In some embodiments, the multi-layered nanostructure comprises at least two shells, and at least one shell comprises ZnSe.
[0039] In some embodiments, the multi-layered nanostructure comprises at least two shells, with at least one shell comprising between about 3 and about 8 monolayers of shell material. In some embodiments, the multi-layered nanostructure comprises at least two shells, with at least one shell comprising between about 3 and about 5 monolayers of shell material.
[0040] In some embodiments, the multi-layered nanostructure has a normalized optical density between about 1.5 and about 8.0. In some embodiments, the multi-layered nanostructure has a normalized optical density between about 1.8 and about 8.0.
[0041]
[0041] In some embodiments, the multilayer nanostructure comprises at least two shells, at least one shell comprises ZnSe, at least one shell comprises between about 3 and about 5 monolayers of shell material, and the nanostructure has a normalized optical density between about 1.3 and about 8.0.
[0042]
[0042] The present invention also provides a multilayered nanostructure comprising a core and at least two shells, at least two shells comprising different shell materials, at least one shell comprising between about 2 and about 10 monolayers of shell material, at least one shell comprising an alloy, and the nanostructure having a normalized optical density between about 1.0 and about 8.0.
[0043] In some embodiments, the multi-layered nanostructured core is selected from the group consisting of ZnO, ZnSe, ZnS, ZnTe, CdO, CdSe, CdS, CdTe, HgO, HgS, HgTe, BN, BP, BAs, BSb, AlN, AlP, AlAs, AlSb, GaN, GaP, GaSb, InN, InP, InAs, and InSb. In some embodiments, the multi-layered nanostructured core is selected from the group consisting of ZnS, ZnSe, CdSe, CdS, and InP. In some embodiments, the multi-layered nanostructured core comprises InP.
[0044] In some embodiments, the multi-layered nanostructure comprises at least two shells, and at least one shell comprises ZnS.
[0045] In some embodiments, the multi-layered nanostructure comprises at least two shells, and at least one shell comprises ZnSe.
[0046] In some embodiments, the multi-layered nanostructure comprises at least two shells, with at least one shell comprising between about 3 and about 8 monolayers of shell material. In some embodiments, the multi-layered nanostructure comprises at least two shells, with at least one shell comprising between about 3 and about 5 monolayers of shell material.
[0047] In some embodiments, the multi-layer nanostructure comprises at least two shells, and at least one shell comprises an alloy comprising ZnS, GaN, ZnSe, AlP, CdS, GaP, ZnTe, AlAs, CdSe, AlSb, CdTe, GaAs, Sn, Ge, or InP. In some embodiments, the multi-layer nanostructure comprises at least two shells, and at least one shell comprises an alloy comprising ZnTe.
[0048] In some embodiments, the multi-layered nanostructure has a normalized optical density between about 1.5 and about 8.0. In some embodiments, the multi-layered nanostructure has a normalized optical density between about 1.8 and about 8.0.
[0049]
[0049] In some embodiments, the multilayer nanostructure comprises at least two shells, at least one shell comprises ZnSe, at least one shell comprises between about 3 and about 5 monolayers of shell material, at least one shell comprises an alloy of ZnTe, and the nanostructure has a normalized optical density between about 1.8 and about 8.0.
[0050] In some embodiments, the method of making the multi-layered nanostructures results in nanostructures having a normalized optical density between about 1.0 and about 8.0.
[0051] In some embodiments, the method for making a multi-layered nanostructure results in a nanostructure comprising at least one shell, where at least one shell comprises between about 3 and about 10 monolayers. In some embodiments, the method for making a multi-layered nanostructure results in a nanostructure comprising at least one shell, where at least one shell comprises between about 3 and about 8 monolayers. In some embodiments, the method for making a multi-layered nanostructure results in a nanostructure comprising at least one shell, where at least one shell comprises between about 3 and about 5 monolayers.
[0052] In some embodiments, the method of making a multi-layered nanostructure results in a nanostructure having a normalized optical density between about 1.5 and about 8.0. In some embodiments, the method of making a multi-layered nanostructure results in a nanostructure having a normalized optical density between about 1.8 and about 8.0. In some embodiments, the method of making a multi-layered nanostructure results in a nanostructure having a normalized optical density between about 1.0 and 8.0.
[0053]
[0053] In some embodiments, the method for making a multi-layered nanostructure results in a nanostructure having at least one shell, where at least one shell comprises between about 3 and about 10 monolayers. In some embodiments, the method for making a multi-layered nanostructure results in a nanostructure having at least one shell, where at least one shell comprises between about 3 and about 8 monolayers. In some embodiments, the method for making a multi-layered nanostructure results in a nanostructure having at least one shell, where at least one shell comprises between about 3 and about 5 monolayers.
[0054] In some embodiments, the method of making a multi-layered nanostructure further comprises contacting with at least one additional component.
[0055]
[0055] In some embodiments, at least one additional component is selected from the group consisting of ZnS, GaN, ZnSe, AlP, CdS, GaP, ZnTe, AlAs, CdSe, AlSb, CdTe, GaAs, Sn, Ge, and InP.
[0056] In some embodiments, the at least one additional component is ZnTe.
[0057] In some embodiments, the method of making multi-layered nanostructures results in nanostructures having a normalized optical density between about 1.5 and about 8.0.
[0058] In some embodiments, the method of making multi-layered nanostructures results in nanostructures having a normalized optical density between about 1.8 and about 8.0.
[0059]
[0059] The present disclosure also provides a molded article comprising the multilayered nanostructures described herein.
[0060] In some embodiments, the molded article is a light emitting diode.
[0061] In some embodiments, the molded articles exhibit an external quantum efficiency (EQE) of between about 6% and about 20%.
[0062] In some embodiments, the molded article exhibits an EQE of between about 8% and about 20%.
[0063] In some embodiments, the molded article has a thermal conductivity of about 3000 cd / m at 7 volts. 2 ~about 6000cd / m 2 The brightness is between .
[0064] In some embodiments, the molded article has a thermal conductivity of about 3500 cd / m at 7 volts. 2 ~About 4500cd / m 2 The brightness is between .
[0065] In some embodiments, the molded article has a solid quantum yield of between about 10% and about 50%.
[0066] In some embodiments, the molded article has a solid quantum yield of between about 30% and about 45%.
[0067] The present disclosure provides a nanostructured shaped article comprising: (a) a first barrier layer; (b) a second barrier layer; (c) a nanostructured layer between a first barrier layer and a second barrier layer, wherein the nanostructure is a multilayer nanostructure comprising a core and at least two shells, at least one shell comprising between about 2 and about 10 monolayers of shell material, and wherein the nanostructure has a normalized optical density between about 1.0 and about 3.0.
[0068] In some embodiments, the nanostructured molded article further comprises a hole injection material.
[0069] In some embodiments, the nanostructured molded article further comprises a hole injection material comprising poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate).
[0070] In some embodiments, the nanostructured molded article further comprises a hole transport material.
[0071] In some embodiments, the nanostructured molded article further comprises a hole transport material comprising poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))].
[0072] In some embodiments, the nanostructured molded article further comprises an electron transport material.
[0073] In some embodiments, the nanostructured molded article further comprises an electron transport material comprising ZnMgO.
[0074]
[0074] In some embodiments, the nanostructured molded articles exhibit an EQE of between about 6% and about 20%.
[0075]
[0075] In some embodiments, the nanostructured molded articles exhibit an EQE of between about 8% and about 20%.
[0076] In some embodiments, the nanostructured molded article has a luminance of about 3000 cd / m at 7 volts. 2~about 6000cd / m 2 The brightness is between .
[0077] In some embodiments, the nanostructured molded article has a luminance of about 3500 cd / m at 7 volts. 2 ~About 4500cd / m 2 The brightness is between .
[0078]
[0078] In some embodiments, the nanostructured molded article comprises a core comprising InP, one shell comprises ZnSe, the ZnSe shell comprises about 4.5 monolayers of shell material, and one shell comprises ZnS, the ZnS shell comprises about 3 monolayers of shell material.
[0079] The present disclosure provides a nanostructured shaped article comprising: (a) a first barrier layer; (b) a second barrier layer; (c) a nanostructured layer between the first barrier layer and the second barrier layer, wherein the nanostructure is a multi-layered nanostructure comprising a core and at least two shells, and at least one shell has a thickness between 0.7 nm and 3.5 nm. [Brief description of the drawings]
[0080] [Figure 1]
[0080] Transmission electron micrographs (TEM) of thin-shell InP quantum dots with target shell thicknesses of 1.3 monolayers of ZnSe and 4.5 monolayers of ZnS fabricated using low-temperature synthesis. The thin-shell InP / ZnSe / ZnS quantum dots have an average particle size of 3.2±0.4 nm. [Diagram 2]
[0081] TEM images of thick-shell InP quantum dots with target shell thicknesses of 3.5 monolayers of ZnSe and 4.5 monolayers of ZnS fabricated using the high temperature method of the present invention. The thick-shell InP / ZnSe / ZnS quantum dots have an average particle size of 5.85±0.99 nm (calculated 6.93 nm) and a particle size range of 3.5 nm to 7.8 nm. [Diagram 3]
[0082] TEM images of thick-shell InP quantum dots with target shell thicknesses of 1.5 monolayers of ZnSe and 7.5 monolayers of ZnS fabricated using the high temperature method of the present invention. The thick-shell InP / ZnSe / ZnS quantum dots have an average particle size of 6.3±0.8 nm (calculated 7.5 nm). [Figure 4]
[0083] 1 shows the absorbance spectra of thin-shell InP quantum dots with 1.3 layers of ZnSe and 4.5 monolayers of ZnS prepared using low-temperature synthesis and thick-shell InP quantum dots with 3.5 monolayers of ZnSe and 4.5 monolayers of ZnS prepared using the high-temperature method of the present invention. Compared to the thin-shell InP / ZnSe / ZnS quantum dots, the absorption in the low wavelength region is greatly increased for the thick shell. [Diagram 5]
[0084] 1 is a graph showing the results of accelerated lifetime testing under high flow blue light exposure over time for thin-shell InP quantum dots with 1.3 monolayers of ZnSe and 4.5 monolayers of ZnS produced using low-temperature synthesis and thick-shell InP quantum dots with 3.5 monolayers of ZnSe and 4.5 monolayers of ZnS produced using the high-temperature method of the present invention. As shown in the graph, the thin-shell InP quantum dots show a rapid drop in expected lifetime of several hundred hours, followed by a decrease. Conversely, the thick-shell quantum dots maintain their initial brightness for several thousand hours, with a delayed onset of degradation. [Figure 6]
[0085] FIG. 1 is a schematic diagram showing the synthesis of InP / ZnSe / ZnS nanoparticles using the high temperature method of the present invention, in which trioctylphosphine selenide (TOPSe) is used as the selenium source. [Figure 7]
[0086] FIG. 1 is a schematic diagram showing the synthesis of InP / ZnSe / ZnS nanoparticles using the high temperature method of the present invention, in which tri-n-butylphosphine selenide (TBPSe) is used as the selenium source. [Figure 8]
[0087] 4 shows the absorption spectra of the following quantum dots at wavelengths from 300 nm to 650 nm: (A) InP core quantum dot; (B) InP core having 1.3 monolayers of ZnSe and 4.5 monolayers of ZnS made using a low temperature method; (C) InP core having 1.5 monolayers of ZnSe made using a high temperature method of the present invention using TOPSe as the selenium source; (D) InP core having 1.5 monolayers of ZnSe and 2.5 monolayers of ZnS made using a high temperature method of the present invention using TOPSe as the selenium source; (E) InP core having 1.5 monolayers of ZnSe and 4.5 monolayers of ZnS made using a high temperature method of the present invention using TOPSe as the selenium source; (F) InP core having 1.5 monolayers of ZnSe and 7.5 monolayers of ZnS made using a high temperature method of the present invention using TOPSe as the selenium source. As shown in these spectra, the InP core quantum dots with thick shells produced using the high temperature method of the present invention have increased absorbance at wavelengths below 360 nm compared to the thin shells produced using the low temperature method. [Figure 9]
[0088] The following quantum dot absorption spectra at wavelengths from 400 nm to 575 nm are shown: (A) InP core quantum dot; (B) InP core with 1.3 layers of ZnSe and 4.5 layers of ZnS made using a low-temperature method; (C) InP core with 1.5 layers of ZnSe made using a high-temperature method of the present invention using TOPSe as the selenium source; (D) InP core with 1.5 layers of ZnSe and 2.5 layers of ZnS made using a high-temperature method of the present invention using TOPSe as the selenium source; (E) InP core with 1.5 layers of ZnSe and 4.5 layers of ZnS made using a high-temperature method of the present invention using TOPSe as the selenium source; (F) InP core with 1.5 layers of ZnSe and 7.5 layers of ZnS made using a high-temperature method of the present invention using TOPSe as the selenium source. As shown in these spectra, increasing the layers of ZnSe results in a red shift, and increasing the layers of ZnS results in a blue shift. [Figure 10]
[0089] Absorption spectra of green InP core quantum dots with (A) 2.5 monolayers of ZnSe and 2.0 monolayers of ZnS, (B) 3.5 monolayers of ZnSe and 2.5 monolayers of ZnS, (C) 4.0 monolayers of ZnSe and 2.5 monolayers of ZnS, and (D) 4.5 monolayers of ZnSe and 2.0 monolayers of ZnS at wavelengths from 400 nm to 575 nm. The spectrum of a blue LED is shown for comparison. [Figure 11]
[0090] Absorption spectra of quantum dots containing a green InP core at wavelengths between 400 nm and 575 nm with target shell thicknesses of (A) 3.5 monolayers of ZnSe0.975Te0.025 and 2.5 monolayers of ZnS; and (B) 3.5 monolayers or ZnSe and 2.5 monolayers of ZnS. The spectrum of a blue LED is shown for comparison. [Figure 12]
[0091] 1 is a graph showing the maximum external quantum efficiency (EQE) as a function of the number of ZnS and ZnSe shell monolayers on InP quantum dots used in quantum dot light-emitting devices. QD-1 is a quantum dot light-emitting device made using an InP quantum dot shell containing 2.5 monolayers of ZnSe shell and 4.5 monolayers of ZnS shell. QD-2 is a quantum dot light-emitting device made using an InP quantum dot containing 4.5 monolayers of ZnSe shell and 3 monolayers of ZnS shell. [Figure 13]
[0092] 1 is a graph showing the quantum yield of a film as a function of the number of ZnS and ZnSe shell monolayers on an InP quantum dot used in a quantum dot light-emitting device. QD-1 is a quantum dot light-emitting device made using an InP quantum dot shell containing 2.5 ZnSe shell monolayers and 4.5 ZnS shell monolayers. QD-2 is a quantum dot light-emitting device made using an InP quantum dot containing 4.5 ZnSe shell monolayers and 3 ZnS shell monolayers. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0081] definition
[0093] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this invention pertains.The following definitions supplement the definitions in the art and are directed to this application, and are not attributable to any related or unrelated, for example, any co-owned patents or applications.Although any methods and materials similar or equivalent to those described herein can be used to carry out the testing of the present invention, the preferred materials and methods are described herein.Therefore, the terms used herein are intended to describe only specific embodiments and are not intended to be limiting.
[0082]
[0094] As used in this specification and the appended claims, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. Thus, for example, reference to "a nanostructure" includes a plurality of such nanostructures, and so forth.
[0083]
[0095] As used herein, the term "about" indicates that the value of a particular quantity varies by ±10% of that value, or optionally ±5% of that value, or in some embodiments, ±1% of the value so recited. For example, "about 100 nm" includes a range of sizes from 90 nm to 110 nm, inclusive.
[0084]
[0096] A "nanostructure" is a structure having at least one region or characteristic dimension that is less than 500 nm. In some embodiments, a nanostructure has a dimension that is less than about 200 nm, less than about 100 nm, less than about 50 nm, less than about 20 nm, or less than about 10 nm. Typically, the region or characteristic dimension is along the shortest axis of the structure. Examples of such structures include nanowires, nanorods, nanotubes, branched nanostructures, nanotetrapods, tripods, bipods, nanocrystals, nanodots, quantum dots, nanoparticles, and the like. Nanostructures can be, for example, substantially crystalline, substantially monocrystalline, polycrystalline, amorphous, or combinations thereof. In some embodiments, each of the three dimensions of a nanostructure has a dimension that is less than about 500 nm, less than about 200 nm, less than about 100 nm, less than about 50 nm, less than about 20 nm, or less than about 10 nm.
[0085]
[0097] The term "heterostructure" when used with respect to nanostructures means a nanostructure characterized by at least two different and / or distinguishable material types. Typically, one region of the nanostructure comprises a first material type, while a second region of the nanostructure comprises a second material type. In certain embodiments, the nanostructure comprises a core of a first material and at least one shell of a second (or third, etc.) material, where the different material types are distributed radially, for example, around the long axis of a nanowire, the long axis of an arm of a branched nanowire, or the center of a nanocrystal. A shell can be considered a shell in that it can, but need not completely, cover adjacent materials, or can be considered a heterostructure with respect to a nanostructure; for example, a nanocrystal characterized by a core of one material covered by small islands of a second material is a heterostructure. In other embodiments, the different material types are distributed in different regions in the nanostructure; for example, along the main (long) axis of a nanowire, or along the long axis of an arm of a branched nanowire. Different regions in a heterostructure can comprise entirely different materials, or the different regions can comprise a base material (eg, silicon) with different dopants or different concentrations of the same dopant.
[0086]
[0098] As used herein, the "diameter" of a nanostructure refers to the diameter of a cross section perpendicular to a first axis of the nanostructure, where the first axis has the greatest difference in length with respect to the second and third axes (the second and third axes being two axes that are approximately the same length as each other). The first axis is not necessarily the longest axis of the nanostructure; for example, in the case of a disk-shaped nanostructure, the cross section is a substantially circular cross section perpendicular to the short longitudinal axis of the disk. If the cross section is not circular, the diameter is the average of the major and minor axes of the cross section. In the case of elongated or high aspect ratio nanostructures such as nanowires, the diameter is measured across a cross section perpendicular to the longest axis of the nanowire. In the case of a spherical nanostructure, the diameter is measured from one side to the other through the center of the sphere.
[0087]
[0099] The term "crystalline" or "substantially crystalline" when used with respect to a nanostructure means that the nanostructure typically exhibits long-range order across one or more dimensions of the structure. One of skill in the art will appreciate that the term "long-range order" is determined by the absolute size of a particular nanostructure, since the order of a single crystal cannot extend beyond the boundaries of the crystal. In this case, "long-range order" refers to substantial order across at least most of the dimensions of the nanostructure. In some cases, the nanostructure may have an oxide or other coating, or may be composed of a core and at least one shell. In such cases, it will be understood that the oxide, shell, or other coating may exhibit such order, but need not exhibit such order (e.g., may be amorphous, polycrystalline, or otherwise). In such cases, the phrases "crystalline," "substantially crystalline," "substantially monocrystalline," or "monocrystalline" refer to the central core of the nanostructure (excluding any coating layers or shells). As used herein, the terms "crystalline" or "substantially crystalline" are intended to include structures that contain various defects, stacking faults, atomic substitutions, and the like, provided that the structure exhibits substantial long-range order (e.g., order over at least about 80% of the length of at least one axis of the nanostructure or its core). Furthermore, it will be understood that the interface between the core and the exterior of the nanostructure, or between the core and an adjacent shell, or between a shell and a second adjacent shell, can include non-crystalline regions and may even be amorphous. This does not prevent a nanostructure from being crystalline or substantially crystalline as defined herein.
[0088]
[0100] When used in reference to a nanostructure, the term "monocrystalline" indicates that the nanostructure is substantially crystalline and comprises substantially a single crystal. When used in reference to a nanostructure heterostructure comprising a core and one or more shells, "monocrystalline" indicates that the core is substantially crystalline and comprises substantially a single crystal.
[0089]
[0101] A "nanocrystal" is a nanostructure that is substantially monocrystalline. Thus, a nanocrystal has at least one region or characteristic dimension that is less than about 500 nm in dimension. In some embodiments, a nanocrystal has a dimension that is less than about 200 nm, less than about 100 nm, less than about 50 nm, less than about 20 nm, or less than about 10 nm. The term "nanocrystal" is intended to include substantially monocrystalline nanostructures that include various defects, stacking faults, atomic substitutions, and the like, as well as substantially monocrystalline nanostructures that are free of such defects, stacking faults, and atomic substitutions. In the case of nanocrystal heterostructures that include a core and one or more shells, the core of the nanocrystal is typically substantially monocrystalline, but the shells need not be monocrystalline. In some embodiments, each of the three dimensions of the nanocrystal has a dimension that is less than about 500 nm, less than about 200 nm, less than about 100 nm, less than about 50 nm, less than about 20 nm, or less than about 10 nm.
[0090]
[0102] The term "quantum dot" (or "dot") refers to a nanocrystal that exhibits quantum or exciton confinement. Quantum dots may be substantially homogeneous in material properties or, in some embodiments, may be heterogeneous, e.g., comprise a core and at least one shell. The optical properties of quantum dots may be affected by their particle size, chemical composition, and / or surface composition, and can be investigated by suitable optical tests available in the art. The ability to tune the size of the nanocrystals, e.g., within a range between about 1 nm and about 15 nm, allows for a photoemission range across the entire optical spectrum, allowing for greater freedom in color rendering.
[0091]
[0103] A "ligand" is a molecule that can interact (either weakly or strongly) with one or more faces of a nanostructure, for example, through covalent interactions, ionic interactions, van der Waals interactions, or other molecular interactions with the surface of the nanostructure.
[0092]
[0104] "Photoluminescence quantum yield" is the ratio of emitted photons to absorbed photons, for example, by a nanostructure or a population of nanostructures. As is well known in the art, quantum yield is typically determined by comparative methods using well-characterized standards with known quantum yield values.
[0093]
[0105] As used herein, the term "monolayer" is a unit of measure of shell thickness derived from the bulk crystal structure of the shell material as the shortest distance between related lattice planes. As an example, for a cubic lattice structure, the thickness of one monolayer is determined as the distance between adjacent lattice planes in the
[0111] direction. As an example, one monolayer of cubic ZnSe corresponds to a thickness of 0.328 nm, and one monolayer of cubic ZnS corresponds to a thickness of 0.31 nm. The thickness of a monolayer of an alloy material can be determined from the alloy composition by Vegard's law.
[0094]
[0106] As used herein, the term "shell" refers to a material deposited on a core or on a previously deposited shell of the same or different composition, resulting from a single deposition act of shell material. The exact shell thickness depends on the material and precursor input and conversion rate, and can be reported in units of nanometers or monolayers. As used herein, "target shell thickness" refers to the shell thickness intended to be used for calculation of the amount of precursor required. As used herein, "actual shell thickness" refers to the amount of shell material actually deposited after synthesis, and can be measured by methods well known in the art. As an example, the actual shell thickness can be measured by comparing the grain size determined from TEM images of nanocrystals before and after shell synthesis.
[0095]
[0107] As used herein, the term "full width at half maximum" (FWHM) is a measure of the size distribution of quantum dots. The emission spectrum of quantum dots generally has the shape of a Gaussian curve. The width of the Gaussian curve is defined as the FWHM, which gives an idea of the size distribution of the particles. A smaller FWHM indicates a narrower quantum dot nanocrystal size. The FWHM also depends on the emission wavelength maximum.
[0096]
[0108] As used herein, the term "external quantum efficiency" (EQE) is the ratio of the number of photons emitted from a light emitting diode (LED) to the number of electrons passing through the device. EQE measures how efficiently a light emitting diode can convert electrons into photons and emit them. EQE is calculated by the formula: EQE = [injection efficiency] × [internal quantum yield] × [extraction efficiency] can be measured using During the ceremony: Injection efficiency = fraction of electrons injected through the device into the active area; Internal quantum yield = the fraction of all electron-hole recombinations in the active region that are radiative and thus generate photons; Extraction efficiency = the fraction of photons generated in the active area that are emitted from the device.
[0097]
[0109] As used herein, "alkyl" refers to a straight or branched saturated aliphatic group having the specified number of carbon atoms. In some embodiments, alkyl is any of the C 1-2 Alkyl, C 1-3 Alkyl, C 1-4 Alkyl, C 1-5 Alkyl, C 1-6 Alkyl, C 1-7 Alkyl, C 1-8 Alkyl, C 1-9 Alkyl, C 1-10 Alkyl, C 1-12 Alkyl, C 1-14 Alkyl, C 1-16 Alkyl, C 1-18 Alkyl, C1-20 Alkyl, C 8-20 Alkyl, C 12-20 Alkyl, C 14-20 Alkyl, C 16-20 Alkyl or C 18-20 It is an alkyl group. For example, C 1-6 Alkyl includes, but is not limited to, methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, pentyl, isopentyl, and hexyl, in some embodiments, alkyl is octyl, nonyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl, nonadecyl, or icosanyl.
[0098]
[0110] Unless otherwise stated, ranges listed are inclusive.
[0099]
[0111] A variety of additional terms are defined or otherwise characterized herein.
[0100] Core Manufacturing
[0112] A variety of methods for colloidal synthesis of nanostructures are known in the art, including techniques for controlling the growth of nanostructures to control, for example, the distribution of sizes and / or shapes of the resulting nanostructures.
[0101]
[0113] In a typical colloidal synthesis, semiconductor nanostructures are formed by rapid injection of pyrolyzed precursors into a hot solution (e.g., hot solvent and / or surfactant). Multiple precursors can be injected simultaneously or sequentially. These precursors react rapidly to form nuclei. Growth of the nanostructures occurs by addition of monomers to the nuclei, typically at a growth temperature lower than the injection / nucleation temperature.
[0102]
[0114] The ligands interact with the surface of the nanostructure. At the growth temperature, rapid adsorption and desorption of the ligands by the nanostructure surface can add and / or remove atoms from the nanostructure while suppressing agglomeration of the growing nanostructure. In general, ligands that weakly coordinate to the nanostructure surface allow for rapid growth of the nanostructure, while ligands that bind more strongly to the nanostructure surface result in slower nanostructure growth. The ligands may also interact with one (or more) precursors to slow down the growth of the nanostructure.
[0103]
[0115] Growth of nanostructures in the presence of one ligand typically results in spherical nanostructures, but using a mixture of two or more ligands allows the growth to be controlled such that non-spherical nanostructures can be formed, for example when two (or more) ligands are separately adsorbed onto separate crystal faces of the growing nanostructure.
[0104]
[0116] Thus, many factors are known to affect nanostructure growth and can be manipulated, independently or in combination, to control the size and / or shape distribution of the resulting nanostructures, including, for example, temperature (nucleation and / or growth), precursor composition, time-dependent precursor concentration, ratio of precursors to each other, surfactant composition, number of surfactants, and ratio of surfactants to each other and / or ratio of surfactant to precursor.
[0105]
[0117] The synthesis of II-VI nanostructures has been described in U.S. Patent No. 6,225,198, U.S. Patent No. 6,322,901, U.S. Patent No. 6,207,229, U.S. Patent No. 6,607,829, U.S. Patent No. 7,060,243, U.S. Patent No. 7,374,824, U.S. Patent No. 6,861,155, U.S. Patent No. 7,125,605, U.S. Patent No. 7,566,476, U.S. Patent No. 8,158,193, and U.S. Patent No. 8,101,234, as well as U.S. Patent Application Publication No. 2011 / 0262752, and U.S. Patent Application Publication No. 2011 / 0263062. In some embodiments, the core is a II-VI nanocrystal selected from the group consisting of ZnO, ZnSe, ZnS, ZnTe, CdO, CdSe, CdS, CdTe, HgO, HgSe, HgS, and HgTe. In some embodiments, the core is a nanocrystal selected from the group consisting of ZnSe, ZnS, CdSe, and CdS.
[0106]
[0118] Although II-VI nanostructures such as CdSe and CdS quantum dots can exhibit desirable luminescence behavior, issues such as the toxicity of cadmium limit the applications in which such nanostructures can be used. Therefore, less toxic alternatives that exhibit favorable luminescence properties are highly desirable. In general, III-V nanostructures, and in particular InP-based nanostructures, are the best-known alternatives to cadmium-based materials due to their compatible emission range.
[0107]
[0119] In some embodiments, the nanostructures are cadmium-free. As used herein, the term "cadmium-free" is intended to mean that the nanostructures contain less than 100 ppm by weight of cadmium. Restriction of Hazardous Substances (RoHS) compliance regulations require that cadmium in homogeneous precursor raw materials should be 0.01% by weight (100 ppm by weight) or less. The cadmium level in the Cd-free nanostructures of the present invention is limited by the trace metal concentration in the precursor material. The trace metal (including cadmium) concentration in the precursor material of the Cd-free nanostructures can be measured by inductively coupled plasma mass spectrometry (ICP-MS) analysis and is present at parts per billion (ppb) levels. In some embodiments, the nanostructures that are "cadmium-free" contain less than about 50 ppm, less than about 20 ppm, less than about 10 ppm, or less than about 1 ppm of cadmium.
[0108]
[0120] In some embodiments, the core is a III-V nanostructure. In some embodiments, the core is a III-V nanocrystal selected from the group consisting of BN, BP, BAs, BSb, AlN, AlP, AlAs, AlSb, GaN, GaP, GaAs, GaSb, InN, InP, InAs, and InSb. In some embodiments, the core is an InP nanocrystal.
[0109]
[0121] The synthesis of III-V nanostructures is described in U.S. Patent No. 5,505,928, U.S. Patent No. 6,306,736, U.S. Patent No. 6,576,291, U.S. Patent No. 6,788,453, U.S. Patent No. 6,821,337, U.S. Patent No. 7,138,098, U.S. Patent No. 7,557,028, U.S. Patent No. 8,062,967, U.S. Patent No. 7,645,397, and U.S. Patent No. 8,282,412, and U.S. Patent Application Publication No. 2015 / 236195. Synthesis of III-V nanostructures is also described in Wells, RL, et al., “The use of tris(trimethylsilyl)arsine to prepare gallium arsenide and indium arsenide,” Chem. Mater. 1:4-6 (1989), and Guzelian, AA, et al., “Colloidal chemical synthesis and characterization of InAs nanocrystal quantum dots,” Appl. Phys. Lett. 69: 1432-1434 (1996).
[0110]
[0122] The synthesis of InP-based nanostructures is described, for example, in Xie, R., et al., “Colloidal InP nanocrystals as efficient emitters covering blue to near-infrared,” J. Am. Chem. Soc. 129:15432-15433 (2007); Micic, O.I., et al., “Core-shell quantum dots of lattice-matched ZnCdSe2 shells on InP cores: Experiment and theory,” J. Phys. Chem. B 104:12149-12156 (2000); Liu, Z., et al., “Coreduction colloidal synthesis of III-V nanocrystals: The case of InP,” Angew. Chem. Int. Ed. Engl. 47:3540-3542 (2008); Li, L. et al., “Economic synthesis of high quality InP nanocrystals using calcium phosphide as the phosphorus precursor,” Chem. Mater. 20:2621-2623 (2008); D. Battaglia and X. Peng, “Formation of high quality InP and InAs nanocrystals in a noncoordinating solvent,” Nano Letters 2:1027-1030 (2002); Kim, S., et al., “Highly luminescent InP / GaP / ZnS nanocrystals and their application to white light-emitting diodes,” J. Am. Chem. Soc. 134:3804-3809 (2012); Nann, T., et al., “Water splitting by visible light: A nanophotocathode for hydrogen production,” Angew.Chem. Int. Ed. 49:1574-1577 (2010);Borchert, H., et al.,“Investigation of ZnS passivated InP nanocrystals by XPS,”Nano Letters 2:151-154 (2002);L. Li and P. Reiss,“One-pot synthesis of highly luminescent InP / ZnS nanocrystals without precursor injection,”J. Am. Chem. Soc. 130:11588-11589 (2008);Hussain, S., et al.“One-pot fabrication of high-quality InP / ZnS (core / shell) quantum dots and their application to cellular imaging,”Chemphyschem. 10:1466-1470 (2009);Xu, S., et al.,“Rapid synthesis of high-quality InP nanocrystals,”J. Am. Chem. Soc. 128:1054-1055 (2006);Micic, O.I., et al.,“Size-dependent spectroscopy of InP quantum dots,”J. Phys. Chem. B 101:4904-4912 (1997);Haubold, S., et al.,“Strongly luminescent InP / ZnS core-shell nanoparticles,”Chemphyschem. 5:331-334 (2001);CrosGagneux, A., et al.,“Surface chemistry of InP quantum dots: A comprehensive study,”J. Am. Chem. Soc. 132:18147-18157 (2010);Micic, O.I., et al., “Synthesis and characterization of InP, GaP, and GalnP2 quantum dots,” J. Phys. Chem. 99:7754-7759 (1995); Guzelian, AA, et al., “Synthesis of size-selected, surface-passivated InP nanocrystals,” J. Phys. Chem. 100:7212-7219 (1996);Lucey, DW, et al.,“Monodispersed InP quantum dots prepared by colloidal chemistry in a non-coordinating solvent,”Chem. Mater. 17:3754-3762 (2005);Lim, J., et al.,“InP@ZnSeS, core@composition gradient shell quantum dots with enhanced stability,”Chem. Mater. 23:4459-4463 (2011);and Zan, F., et al., “Experimental studies on blinking behavior of single InP / ZnS quantum dots: Effects of synthetic conditions and UV irradiation,” J. Phys. Chem. C 116:394-3950 (2012). However, such efforts have had only limited success in producing InP nanostructures with high quantum yields.
[0111]
[0123] In some embodiments, the core is doped. In some embodiments, the dopant of the nanocrystalline core comprises a metal, such as one or more transition metals. In some embodiments, the dopant is a transition metal selected from the group consisting of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mn, Tc, Re, Fe, Ru, Os, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, and combinations thereof. In some embodiments, the dopant comprises a non-metal. In some embodiments, the dopant is ZnS, ZnSe, ZnTe, CdSe, CdS, CdTe, HgS, HgSe, HgTe, CuInS2, CuInSe2, AlN, AlP, AlAs, GaN, GaP, or GaAs.
[0112]
[0124] In some embodiments, the cores are purified prior to depositing the shell, hi some embodiments, filtration of the cores is performed to remove precipitates from the core solution.
[0113]
[0125] In some embodiments, an acid etching step of the core is performed prior to depositing the shell.
[0114]
[0126] In some embodiments, the diameter of the core is determined using quantum confinement. Quantum confinement in zero-dimensional nanocrystallites, such as quantum dots, arises from the spatial confinement of electrons within the crystallite boundaries. Quantum confinement can be observed when the diameter of the material becomes as large as the de Broglie wavelength of the wave function. The electronic and optical properties of nanoparticles deviate substantially from those of bulk materials. When the confinement dimension is larger than the wavelength of the particle, the particle behaves as if it were free. During this state, the band gap remains at its original energy due to the continuous energy states. However, as the confinement dimension decreases and reaches a certain limit, typically the nanoscale, the energy spectrum becomes discrete. As a result, the band gap becomes size-dependent.
[0115] Shell Creation
[0127] In some embodiments, the nanostructures of the present invention comprise a core and at least one shell. In some embodiments, the nanostructures of the present invention comprise a core and at least two shells. The shell can, for example, increase the quantum yield and / or stability of the nanostructure. In some embodiments, the core and shell comprise different materials. In some embodiments, the nanostructures comprise multiple shells of different shell materials.
[0116]
[0128] In some embodiments, a shell comprising a mixture of group II and group VI elements is deposited on the core or core / shell structure. In some embodiments, the shell is deposited by at least two mixtures from a zinc source, a selenium source, a sulfur source, a tellurium source, and a cadmium source. In some embodiments, the shell is deposited by two mixtures from a zinc source, a selenium source, a sulfur source, a tellurium source, and a cadmium source. In some embodiments, the shell is deposited by three mixtures from a zinc source, a selenium source, a sulfur source, a tellurium source, and a cadmium source. In some embodiments, the shell is composed of zinc and sulfur; zinc and selenium; zinc, sulfur, and selenium; zinc and tellurium; zinc, tellurium, and sulfur; zinc, tellurium, and selenium; zinc, cadmium, and sulfur; zinc, cadmium, and selenium; cadmium and sulfur; cadmium and selenium; cadmium, selenium, and sulfur; cadmium, zinc, and sulfur; cadmium, zinc, and selenium; or cadmium, zinc, sulfur, and selenium.
[0117]
[0129] In some embodiments, the shell comprises more than one monolayer of shell material. This number of monolayers is an average across all nanostructures; therefore, the number of monolayers in a shell can be a fraction. In some embodiments, the number of monolayers in the shell is between 0.25-10, between 0.25-8, between 0.25-7, between 0.25-6, between 0.25-5, between 0.25-4, between 0.25-3, between 0.25-2, between 2-10, between 2-8, between 2-7, between 2-6, between 2-5, between 2-4, between 2-3, between 3-10, between 3-8, between 3-7, between 3-6, between 3-5, between 3-4, between 4-10, between 4-8, between 4-7, between 4-6, between 4-5, between 5-10, between 5-8, between 5-7, between 5-6, between 6-10, between 6-8, between 6-7, between 7-10, between 7-8, or between 8-10. In some embodiments, the shell comprises between 3 and 5 monolayers.
[0118]
[0130] In some embodiments, the number of monolayers in the shell is between 0.25 and 12. In some embodiments, the number of monolayers in the shell is between 0.25 and 12, between 0.25 and 10, between 0.25 and 8, between 0.25 and 7, between 0.25 and 6, between 0.25 and 5, between 0.25 and 4, between 0.25 and 3, or between 0.25 and 2.
[0119]
[0131] The thickness of the shell can be controlled by varying the amount of precursors provided. For a particular shell thickness, at least one precursor is optionally provided in an amount that results in a shell of a predetermined thickness when the growth reaction is substantially complete. When two or more different precursors are provided, the amount of each precursor can be limited, or one precursor can be provided in a limited amount and the other precursor provided in excess.
[0120]
[0132] The thickness of each shell can be determined using techniques known to those of skill in the art. In some embodiments, the thickness of each shell is determined by comparing the average diameter of the nanostructures before and after adding each shell. In some embodiments, the average diameter of the nanostructures before and after adding each shell is determined by TEM. In some embodiments, each shell has a thickness between 0.05 nm and 3.5 nm, between 0.05 nm and 2 nm, between 0.05 nm and 0.9 nm, between 0.05 nm and 0.7 nm, between 0.05 nm and 0.5 nm, between 0.05 nm and 0.3 nm, between 0.05 nm and 0.1 nm, between 0.1 nm and 3.5 nm, between 0.1 nm and 2 nm, between 0.1 nm and 0.9 nm, between 0.1 nm and 0.7 nm, between 0.1 nm and 0.5 nm, between 0.1 nm and 0.3 nm, between 0.3 The thickness may be between 0.3 nm and 3.5 nm, between 0.3 nm and 2 nm, between 0.3 nm and 0.9 nm, between 0.3 nm and 0.7 nm, between 0.3 nm and 0.5 nm, between 0.5 nm and 3.5 nm, between 0.5 nm and 2 nm, between 0.5 nm and 0.9 nm, between 0.5 nm and 0.7 nm, between 0.7 nm and 3.5 nm, between 0.7 nm and 2 nm, between 0.7 nm and 0.9 nm, between 0.9 nm and 3.5 nm, between 0.9 nm and 2 nm, or between 2 nm and 3.5 nm.
[0121]
[0133] In some embodiments, each shell has a thickness between 0.05 nm and 4.5 nm, between 0.1 nm and 4.5 nm, between 0.3 nm and 4.5 nm, between 0.5 nm and 4.5 nm, between 0.7 nm and 4.5 nm, between 0.9 nm and 4.5 nm, between 2 nm and 4.5 nm, or between 3.5 nm and 4.5 nm.
[0122]
[0134] In some embodiments, each shell is synthesized in the presence of at least one nanostructure ligand. The ligand can, for example, improve the compatibility of the nanostructures with a solvent or polymer (so that the nanostructures can be dispersed throughout the composition so that they do not clump together), increase the quantum yield of the nanostructures, and / or maintain the luminescence of the nanostructures (e.g., when the nanostructures are incorporated into a matrix). In some embodiments, the ligands for the synthesis of the core and the shell are the same. In some embodiments, the ligands for the synthesis of the core and the shell are different. After synthesis, any ligands on the surface of the nanostructure can be exchanged for another ligand with other desirable properties. Exemplary ligands are described in U.S. Pat. No. 7,572,395, U.S. Pat. No. 8,143,703, U.S. Pat. No. 8,425,803, U.S. Pat. No. 8,563,133, U.S. Pat. No. 8,916,064, U.S. Pat. No. 9,005,480, U.S. Pat. No. 9,139,770, and U.S. Pat. No. 9,169,435, and U.S. Patent Application Publication No. 2008 / 0118755.
[0123]
[0135] Ligands suitable for the synthesis of the shell are well known to those skilled in the art. In some embodiments, the ligand is a fatty acid selected from the group consisting of lauric acid, caproic acid, myristic acid, palmitic acid, stearic acid, and oleic acid. In some embodiments, the ligand is an organophosphine or organophosphine oxide selected from trioctylphosphine oxide (TOPO), trioctylphosphine (TOP), diphenylphosphine (DPP), triphenylphosphine oxide, and tributylphosphine oxide. In some embodiments, the ligand is an amine selected from the group consisting of dodecylamine, oleylamine, hexadecylamine, dioctylamine, and octadecylamine. In some embodiments, the ligand is tributylphosphine, oleic acid, or zinc oleate.
[0124]
[0136] In some embodiments, each shell is formed in the presence of a mixture of ligands. In some embodiments, each shell is formed in the presence of a mixture that includes two, three, four, five, or six different ligands. In some embodiments, each shell is formed in the presence of a mixture that includes three different ligands. In some embodiments, the mixture of ligands includes tributylphosphine, oleic acid, and zinc oleate.
[0125]
[0137] In some embodiments, each shell is formed in the presence of a solvent. In some embodiments, the solvent is selected from the group consisting of 1-octadecene, 1-hexadecene, 1-eicosene, eicosane, octadecane, hexadecane, tetradecane, squalene, squalane, trioctylphosphine oxide, and dioctyl ether. In some embodiments, the solvent is 1-octadecene.
[0126]
[0138] In some embodiments, the core or core / shell and the shell precursor are heated at 20° C. to 310° C., 20° C. to 280° C., 20° C. to 250° C., 20° C. to 200° C., 20° C. to 150° C., 20° C. to 100° C., 20° C. to 50° C., 50° C. to 310° C., 50° C. to 280° C., 50° C. to 250° C., 50° C. to 200° C., 50° C. to 150° C., 50° C. to 100° C., 100° C. to 310° C. The contact may be performed at an addition temperature between 20° C. and 280° C., between 100° C. and 250° C., between 100° C. and 20 ...150° C., between 150° C. and 310° C., between 150° C. and 280° C., between 150° C. and 250° C., between 150° C. and 200° C., between 200° C. and 310° C., between 200° C. and 280° C., between 200° C. and 250° C., between 250° C. and 310° C., between 250° C. and 280° C., or between 280° C. and 310° C. In some embodiments, the core or core / shell and the shell precursor are contacted at an addition temperature between 20° C. and 100° C.
[0127]
[0139] In some embodiments, after contacting the core or core / shell with the shell precursor, the temperature of the reaction mixture is increased to an elevated temperature between 200° C. and 310° C., between 200° C. and 280° C., between 200° C. and 250° C., between 200° C. and 220° C., between 220° C. and 310° C., between 220° C. and 280° C., between 220° C. and 250° C., between 250° C. and 310° C., between 250° C. and 280° C., or between 280° C. and 310° C. In some embodiments, after contacting the core or core / shell with the shell precursor, the temperature of the reaction mixture is increased to an elevated temperature between 250° C. and 310° C.
[0128]
[0140] In some embodiments, the time for the temperature to reach the above-mentioned high temperature after contacting the core or core / shell with the shell precursor is between 2 and 240 minutes, between 2 and 200 minutes, between 2 and 100 minutes, between 2 and 60 minutes, between 2 and 40 minutes, between 5 and 240 minutes, between 5 and 200 minutes, between 5 and 100 minutes, between 5 and 60 minutes, between 5 and 40 minutes, between 10 and 240 minutes, between 10 and 200 minutes, between 10 and 100 minutes, between 10 and 60 minutes, between 10 and 40 minutes, between 40 and 240 minutes, between 40 and 200 minutes, between 40 and 100 minutes, between 40 and 60 minutes, between 60 and 240 minutes, between 60 and 200 minutes, between 60 and 100 minutes, between 100 and 240 minutes, between 100 and 200 minutes, or between 200 and 240 minutes.
[0129]
[0141] In some embodiments, after contacting the core or core / shell with the shell precursor, the temperature of the reaction mixture is maintained at an elevated temperature for 2 to 240 minutes, 2 to 200 minutes, 2 to 100 minutes, 2 to 60 minutes, 2 to 40 minutes, 5 to 240 minutes, 5 to 200 minutes, 5 to 100 minutes, 5 to 60 minutes, 5 to 40 minutes, 10 to 240 minutes, 10 to 200 minutes, 10 to 100 minutes, 10 to 60 minutes, 10 to 40 minutes, 40 to 240 minutes, 40 to 200 minutes, 40 to 100 minutes, 40 to 60 minutes, 60 to 240 minutes, 60 to 200 minutes, 60 to 100 minutes, 100 to 240 minutes, 100 to 200 minutes, or 200 to 240 minutes. In some embodiments, after contacting the core or core / shell with the shell precursor, the temperature of the reaction mixture is maintained at an elevated temperature for a period of 30 to 120 minutes.
[0130]
[0142] In some embodiments, additional shells are formed by further addition of shell material precursors that are added to the reaction mixture and subsequently maintained at elevated temperatures. Typically, additional shell precursors are provided after the reaction of the previous shell is substantially complete (e.g., when at least one of the previous precursors has run out or been removed from the reaction, or when no further growth can be detected). Further addition of precursors results in the formation of additional shells.
[0131]
[0143] In some embodiments, the nanostructures are cooled before adding additional shell material precursors to obtain additional shells. In some embodiments, the nanostructures are maintained at elevated temperatures before adding additional shell material precursors to obtain additional shells.
[0132]
[0144] After a sufficient layer of the shell has been added so that the nanostructure reaches a desired thickness and diameter, the nanostructure can be cooled. In some embodiments, the core / shell nanostructure is cooled to room temperature. In some embodiments, an organic solvent is added to dilute the reaction mixture containing the core / shell nanostructure.
[0133]
[0145] In some embodiments, the organic solvent used to dilute the reaction mixture is ethanol, hexane, pentane, toluene, benzene, diethyl ether, acetone, ethyl acetate, dichloromethane (methylene chloride), chloroform, dimethylformamide, or N-methylpyrrolidinone, hi some embodiments, the organic solvent is toluene.
[0134]
[0146] In some embodiments, the core / shell nanostructures are isolated. In some embodiments, the core / shell nanostructures are isolated by precipitation with an organic solvent. In some embodiments, the core / shell nanostructures are isolated by coagulation with ethanol.
[0135]
[0147] The number of monolayers determines the size of the core / shell nanostructure. The size of the core / shell nanostructure can be determined using techniques known to those of skill in the art. In some embodiments, the size of the core / shell nanostructure is determined using TEM. In some embodiments, the core / shell nanostructures have an average diameter between 1 nm and 15 nm, between 1 nm and 10 nm, between 1 nm and 9 nm, between 1 nm and 8 nm, between 1 nm and 7 nm, between 1 nm and 6 nm, between 1 nm and 5 nm, between 5 nm and 15 nm, between 5 nm and 10 nm, between 5 nm and 9 nm, between 5 nm and 8 nm, between 5 nm and 7 nm, between 5 nm and 6 nm, between 6 nm and 15 nm, between 6 nm and 10 nm, between 6 nm and 9 nm, between 6 nm and 8 nm, between 6 nm and 7 nm, between 7 nm and 15 nm, between 7 nm and 10 nm, between 7 nm and 9 nm, between 7 nm and 8 nm, between 8 nm and 10 nm, between 8 nm and 9 nm, between 9 nm and 15 nm, between 9 nm and 10 nm, or between 10 nm and 15 nm. In some embodiments, the core / shell nanostructures have an average diameter between 6 nm and 7 nm.
[0136]
[0148] In some embodiments, an acid etching step of the core / shell nanostructure is performed before depositing a further shell.
[0137] Fabrication of ZnSe shell
[0149] In some embodiments, the shell deposited on the core or core / shell nanostructure is a ZnSe shell.
[0138]
[0150] In some embodiments, the shell precursor that is contacted with the core or core / shell nanostructure to form the ZnSe shell comprises a zinc source and a selenium source.
[0139]
[0151] In some embodiments, the zinc source is a dialkyl zinc compound. In some embodiments, the zinc source is a zinc carboxylate. In some embodiments, the zinc source is diethyl zinc, dimethyl zinc, zinc acetate, zinc acetylacetonate, zinc iodide, zinc bromide, zinc chloride, zinc fluoride, zinc carbonate, zinc cyanide, zinc nitrate, zinc oleate, zinc oxide, zinc peroxide, zinc perchlorate, zinc sulfate, zinc hexanoate, zinc octanoate, zinc laurate, zinc myristate, zinc palmitate, zinc stearate, zinc dithiocarbamate, or mixtures thereof. In some embodiments, the zinc source is zinc oleate, zinc hexanoate, zinc octanoate, zinc laurate, zinc myristate, zinc palmitate, zinc stearate, zinc dithiocarbamate, or mixtures thereof. In some embodiments, the zinc source is zinc oleate.
[0140]
[0152] In some embodiments, the selenium source is an alkyl-substituted selenourea. In some embodiments, the selenium source is a phosphine selenide. In some embodiments, the selenium source is selected from trioctylphosphine selenide, tri(n-butyl)phosphine selenide, tri(sec-butyl)phosphine selenide, tri(tert-butyl)phosphine selenide, trimethylphosphine selenide, triphenylphosphine selenide, diphenylphosphine selenide, phenylphosphine selenide, tricyclohexylphosphine selenide, cyclohexylphosphine selenide, 1-octaneselenol, 1-dodecaneselenol, selenophenol, elemental selenium, hydrogen selenide, bis(trimethylsilyl)selenide, selenourea, and mixtures thereof. In some embodiments, the selenium source is tri(n-butyl)phosphine selenide, tri(sec-butyl)phosphine selenide, or tri(tert-butyl)phosphine selenide. In some embodiments, the selenium source is trioctylphosphine selenide.
[0141]
[0153] In some embodiments, the molar ratio of the core to the zinc source for forming the ZnSe shell is between 1:2 and 1:1000, between 1:2 and 1:100, between 1:2 and 1:50, between 1:2 and 1:25, between 1:2 and 1:15, between 1:2 and 1:10, between 1:2 and 1:5, between 1:5 and 1:1000, between 1:5 and 1:100, between 1:5 and 1:50, between 1:5 and 1:25, between 1:5 and 1:15, between 1:5 and 1:10, between 1:10 and 1:10 between 1:10 and 1:100, between 1:10 and 1:50, between 1:10 and 1:25, between 1:10 and 1:15, between 1:15 and 1:1000, between 1:15 and 1:100, between 1:15 and 1:50, between 1:15 and 1:25, between 1:25 and 1:1000, between 1:25 and 1:100, between 1:25 and 1:50, or between 1:50 and 1:1000, between 1:50 and 1:100, between 1:100 and 1:1000.
[0142]
[0154] In some embodiments, the molar ratio of the core to the selenium source for forming the ZnSe shell is between 1:2 and 1:1000, between 1:2 and 1:100, between 1:2 and 1:50, between 1:2 and 1:25, between 1:2 and 1:15, between 1:2 and 1:10, between 1:2 and 1:5, between 1:5 and 1:1000, between 1:5 and 1:100, between 1:5 and 1:50, between 1:5 and 1:25, between 1:5 and 1:15, between 1:5 and 1:10, between 1:10 and 1:10 between 1:10 and 1:100, between 1:10 and 1:50, between 1:10 and 1:25, between 1:10 and 1:15, between 1:15 and 1:1000, between 1:15 and 1:100, between 1:15 and 1:50, between 1:15 and 1:25, between 1:25 and 1:1000, between 1:25 and 1:100, between 1:25 and 1:50, or between 1:50 and 1:1000, between 1:50 and 1:100, between 1:100 and 1:1000.
[0143]
[0155] In some embodiments, the number of monolayers in the ZnSe shell is between 0.25-10, between 0.25-8, between 0.25-7, between 0.25-6, between 0.25-5, between 0.25-4, between 0.25-3, between 0.25-2, between 2-10, between 2-8, between 2-7, between 2-6, between 2-5, between 2-4, between 2-3, between 3-10, between 3-8, between 3-7, between 3-6, between 3-5, between 3-4, between 4-10, between 4-8, between 4-7, between 4-6, between 4-5, between 5-10, between 5-8, between 5-7, between 5-6, between 6-10, between 6-8, between 6-7, between 7-10, between 7-8, or between 8-10. In some embodiments, the ZnSe shell comprises between 2 and 6 monolayers. In some embodiments, the ZnSe shell comprises between 3 and 4 monolayers.
[0144]
[0156] In some embodiments, the number of monolayers in the ZnSe shell is between 0.25 and 12. In some embodiments, the number of monolayers in the ZnSe shell is between 0.25 and 12, between 0.25 and 10, between 0.25 and 8, between 0.25 and 7, between 0.25 and 6, between 0.25 and 5, between 0.25 and 4, between 0.25 and 3, or between 0.25 and 2.
[0145]
[0157] In some embodiments, the ZnSe monolayer has a thickness of about 0.328 nm.
[0146]
[0158] In some embodiments, the ZnSe shell has a thickness between 0.08 nm and 3.5 nm, between 0.08 nm and 2 nm, between 0.08 nm and 0.9 nm, between 0.08 nm and 0.7 nm, between 0.08 nm and 0.5 nm, between 0.08 nm and 0.2 nm, between 0.2 nm and 3.5 nm, between 0.2 nm and 2 nm, between 0.2 nm and 0.9 nm, between 0.2 nm and 0.7 nm, between 0.2 nm and 0.5 nm, between 0.5 nm and 3.5 nm, between 0.5 nm and 2 nm, between 0.5 nm and 0.9 nm, between 0.5 nm and 0.7 nm, between 0.7 nm and 3.5 nm, between 0.7 nm and 2 nm, between 0.7 nm and 0.9 nm, between 0.9 nm and 3.5 nm, between 0.9 nm and 2 nm, or between 2 nm and 3.5 nm.
[0147]
[0159] In some embodiments, the ZnSe shell has a thickness between 0.08 nm and 3.9 nm, between 0.2 nm and 3.9 nm, between 0.5 nm and 3.9 nm, between 0.7 nm and 3.9 nm, between 0.9 nm and 3.9 nm, between 2 nm and 3.9 nm, or between 3.5 nm and 3.9 nm.
[0148] ZnSe x S 1-x Shell Creation
[0160] In some embodiments, the highly luminescent nanostructures include a shell layer between the inner shell and the outer shell. x S 1-x Shell included, in which 0 <x<1である。
[0149]
[0161] In some embodiments, the nanostructures are ZnSe x S 1-x The shell comprises a hydroxyl group, wherein x is between 0 and 1. In some embodiments, x is between 0.01 and 0.99. In some embodiments, x is between 0.25 and 1, between 0.25 and 0.75, between 0.25 and 0.5, between 0.5 and 1, between 0.5 and 0.75, or between 0.75 and 1. In some embodiments, x is 0.5.
[0150]
[0162] In some embodiments, ZnSe x S 1-x The shell relieves the lattice distortion between the ZnSe and ZnS shells.
[0151]
[0163] In some embodiments, ZnSe x S 1-x The x of the shell gradually decreases from the interior to the exterior of the resulting nanostructure.
[0152]
[0164] In some embodiments, ZnSe x S 1-x The shell precursor that is contacted with the core or core / shell to form the shell layer includes a zinc source, a selenium source, and a sulfur source.
[0153]
[0165] In some embodiments, the zinc source is a dialkyl zinc compound. In some embodiments, the zinc source is a zinc carboxylate. In some embodiments, the zinc source is diethyl zinc, dimethyl zinc, zinc acetate, zinc acetylacetonate, zinc iodide, zinc bromide, zinc chloride, zinc fluoride, zinc carbonate, zinc cyanide, zinc nitrate, zinc oleate, zinc oxide, zinc peroxide, zinc perchlorate, zinc sulfate, zinc hexanoate, zinc octanoate, zinc laurate, zinc myristate, zinc palmitate, zinc stearate, zinc dithiocarbamate, or mixtures thereof. In some embodiments, the zinc source is zinc oleate, zinc hexanoate, zinc octanoate, zinc laurate, zinc myristate, zinc palmitate, zinc stearate, zinc dithiocarbamate, or mixtures thereof. In some embodiments, the zinc source is zinc oleate.
[0154]
[0166] In some embodiments, the selenium source is an alkyl-substituted selenourea. In some embodiments, the selenium source is a phosphine selenide. In some embodiments, the selenium source is selected from trioctylphosphine selenide, tri(n-butyl)phosphine selenide, tri(sec-butyl)phosphine selenide, tri(tert-butyl)phosphine selenide, trimethylphosphine selenide, triphenylphosphine selenide, diphenylphosphine selenide, phenylphosphine selenide, tricyclohexylphosphine selenide, cyclohexylphosphine selenide, 1-octaneselenol, 1-dodecaneselenol, selenophenol, elemental selenium, hydrogen selenide, bis(trimethylsilyl)selenide, selenourea, and mixtures thereof. In some embodiments, the selenium source is tri(n-butyl)phosphine selenide, tri(sec-butyl)phosphine selenide, or tri(tert-butyl)phosphine selenide. In some embodiments, the selenium source is trioctylphosphine selenide.
[0155]
[0167] In some embodiments, the sulfur source is selected from elemental sulfur, octanethiol, dodecanethiol, octadecanethiol, tributylphosphine sulfide, cyclohexyl isothiocyanate, α-toluenethiol, ethylene trithiocarbonate, allyl mercaptan, bis(trimethylsilyl) sulfide, trioctylphosphine sulfide, and mixtures thereof. In some embodiments, the sulfur source is an alkyl-substituted zinc dithiocarbamate. In some embodiments, the sulfur source is octanethiol.
[0156] Fabrication of ZnS shell
[0168] In some embodiments, the shell deposited on the core or core / shell nanostructure is a ZnS shell.
[0157]
[0169] In some embodiments, the shell precursor that is contacted with the core or core / shell nanostructure to form the ZnS shell comprises a zinc source and a sulfur source.
[0158]
[0170] In some embodiments, the ZnS shell passivates defects at the particle surface, thereby improving quantum yields and providing higher efficiency when used in devices such as LEDs and lasers. Additionally, spectral impurities caused by defect states can be eliminated by passivation, thereby improving color saturation.
[0159]
[0171] In some embodiments, the zinc source is a dialkyl zinc compound. In some embodiments, the zinc source is a zinc carboxylate. In some embodiments, the zinc source is diethyl zinc, dimethyl zinc, zinc acetate, zinc acetylacetonate, zinc iodide, zinc bromide, zinc chloride, zinc fluoride, zinc carbonate, zinc cyanide, zinc nitrate, zinc oleate, zinc oxide, zinc peroxide, zinc perchlorate, zinc sulfate, zinc hexanoate, zinc octanoate, zinc laurate, zinc myristate, zinc palmitate, zinc stearate, zinc dithiocarbamate, or mixtures thereof. In some embodiments, the zinc source is zinc oleate, zinc hexanoate, zinc octanoate, zinc laurate, zinc myristate, zinc palmitate, zinc stearate, zinc dithiocarbamate, or mixtures thereof. In some embodiments, the zinc source is zinc oleate.
[0160]
[0172] In some embodiments, the zinc source is generated by reacting a zinc salt with a carboxylic acid. In some embodiments, the carboxylic acid is acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, heptanoic acid, caprylic acid, capric acid, undecanoic acid, lauric acid, myristic acid, palmitic acid, stearic acid, behenic acid, acrylic acid, methacrylic acid, but-2-enoic acid, but-3-enoic acid, pent-2-enoic acid, pent-4-enoic acid, hex-2-enoic acid, hex-3-enoic acid, hex-4-enoic acid, hex-5-enoic acid, hepta-6-enoic acid, hexa ... The carboxylic acid is selected from the group consisting of 1-enoic acid, oct-2-enoic acid, dec-2-enoic acid, undec-10-enoic acid, dodec-5-enoic acid, oleic acid, gadoleic acid, erucic acid, linoleic acid, α-linolenic acid, calendic acid, eicosadienoic acid, eicosatrienoic acid, arachidonic acid, stearidonic acid, benzoic acid, paratoluic acid, orthotoluic acid, metatoluic acid, hydrocinnamic acid, naphthenic acid, cinnamic acid, paratoluenesulfonic acid, and mixtures thereof.
[0161]
[0173] In some embodiments, the sulfur source is selected from elemental sulfur, octanethiol, dodecanethiol, octadecanethiol, tributylphosphine sulfide, cyclohexyl isothiocyanate, α-toluenethiol, ethylene trithiocarbonate, allyl mercaptan, bis(trimethylsilyl) sulfide, trioctylphosphine sulfide, and mixtures thereof. In some embodiments, the sulfur source is an alkyl-substituted zinc dithiocarbamate. In some embodiments, the sulfur source is octanethiol. In some embodiments, the sulfur source is dodecanethiol.
[0162]
[0174] In some embodiments, the molar ratio of the core to the zinc source for forming the ZnS shell is between 1:2 and 1:1000, between 1:2 and 1:100, between 1:2 and 1:50, between 1:2 and 1:25, between 1:2 and 1:15, between 1:2 and 1:10, between 1:2 and 1:5, between 1:5 and 1:1000, between 1:5 and 1:100, between 1:5 and 1:50, between 1:5 and 1:25, between 1:5 and 1:15, between 1:5 and 1:10, between 1:10 and 1: between 1:10 and 1:100, between 1:10 and 1:50, between 1:10 and 1:25, between 1:10 and 1:15, between 1:15 and 1:1000, between 1:15 and 1:100, between 1:15 and 1:50, between 1:15 and 1:25, between 1:25 and 1:1000, between 1:25 and 1:100, between 1:25 and 1:50, or between 1:50 and 1:1000, between 1:50 and 1:100, between 1:100 and 1:1000.
[0163]
[0175] In some embodiments, the molar ratio of the core to the sulfur source for forming the ZnS shell is between 1:2 and 1:1000, between 1:2 and 1:100, between 1:2 and 1:50, between 1:2 and 1:25, between 1:2 and 1:15, between 1:2 and 1:10, between 1:2 and 1:5, between 1:5 and 1:1000, between 1:5 and 1:100, between 1:5 and 1:50, between 1:5 and 1:25, between 1:5 and 1:15, between 1:5 and 1:10, between 1:10 and 1: between 1:10 and 1:100, between 1:10 and 1:50, between 1:10 and 1:25, between 1:10 and 1:15, between 1:15 and 1:1000, between 1:15 and 1:100, between 1:15 and 1:50, between 1:15 and 1:25, between 1:25 and 1:1000, between 1:25 and 1:100, between 1:25 and 1:50, or between 1:50 and 1:1000, between 1:50 and 1:100, between 1:100 and 1:1000.
[0164]
[0176] In some embodiments, the number of monolayers in the ZnS shell is between 0.25-10, between 0.25-8, between 0.25-7, between 0.25-6, between 0.25-5, between 0.25-4, between 0.25-3, between 0.25-2, between 2-10, between 2-8, between 2-7, between 2-6, between 2-5, between 2-4, between 2-3, between 3-10, between 3-8, between 3-7, between 3-6, between 3-5, between 3-4, between 4-10, between 4-8, between 4-7, between 4-6, between 4-5, between 5-10, between 5-8, between 5-7, between 5-6, between 6-10, between 6-8, between 6-7, between 7-10, between 7-8, or between 8-10. In some embodiments, the ZnS shell comprises between 2-12 monolayers. In some embodiments, the ZnS shell comprises between 4 and 6 monolayers.
[0165]
[0177] In some embodiments, the number of monolayers in the ZnS shell is between 0.25 and 12. In some embodiments, the number of monolayers in the ZnS shell is between 0.25 and 12, between 0.25 and 10, between 0.25 and 8, between 0.25 and 7, between 0.25 and 6, between 0.25 and 5, between 0.25 and 4, between 0.25 and 3, or between 0.25 and 2.
[0166]
[0178] In some embodiments, the ZnS monolayer has a thickness of about 0.31 nm.
[0167]
[0179] In some embodiments, the ZnS shell has a thickness between 0.08 nm and 3.5 nm, between 0.08 nm and 2 nm, between 0.08 nm and 0.9 nm, between 0.08 nm and 0.7 nm, between 0.08 nm and 0.5 nm, between 0.08 nm and 0.2 nm, between 0.2 nm and 3.5 nm, between 0.2 nm and 2 nm, between 0.2 nm and 0.9 nm, between 0.2 nm and 0.7 nm, between 0.2 nm and 0.5 nm, between 0.5 nm and 3.5 nm, between 0.5 nm and 2 nm, between 0.5 nm and 0.9 nm, between 0.5 nm and 0.7 nm, between 0.7 nm and 3.5 nm, between 0.7 nm and 2 nm, between 0.7 nm and 0.9 nm, between 0.9 nm and 3.5 nm, between 0.9 nm and 2 nm, or between 2 nm and 3.5 nm.
[0168]
[0180] In some embodiments, the ZnS shell has a thickness between 0.08 nm and 3.7 nm, between 0.2 nm and 3.7 nm, between 0.5 nm and 3.7 nm, between 0.7 nm and 3.7 nm, between 0.9 nm and 3.7 nm, between 2 nm and 3.7 nm, or between 3.5 nm and 3.7 nm.
[0169] Core / shell nanostructures
[0181] In some embodiments, the core / shell nanostructure is a core / ZnSe / ZnS nanostructure or a core / ZnSe / ZnSe x S 1-x In some embodiments, the core / shell nanostructure is an InP / ZnSe / ZnS nanostructure or an InP / ZnSe / ZnSe x S 1-x / ZnS nanostructure.
[0170]
[0182] In some embodiments, the core / shell nanostructures exhibit high photoluminescence quantum yields. In some embodiments, the core / shell nanostructures exhibit a photoluminescence quantum yield of between 60%-99%, between 60%-95%, between 60%-90%, between 60%-85%, between 60%-80%, between 60%-70%, between 70%-99%, between 70%-95%, between 70%-90%, between 70%-85%, between 70%-80%, between 80%-99%, between 80%-95%, between 80%-90%, between 80%-85%, between 85%-99%, between 85%-95%, between 80%-85%, between 85%-99%, between 85%-90%, between 85%-90%, between 90%-99%, between 90%-95%, or between 95%-99%. In some embodiments, the core / shell nanostructures exhibit a photoluminescence quantum yield of between 85% and 96%.
[0171]
[0183] The photoluminescence spectrum of the core / shell nanostructure can span substantially any desired portion of the spectrum. In some embodiments, the photoluminescence spectrum of the core / shell nanostructure has an emission maximum between 300 nm and 750 nm, between 300 nm and 650 nm, between 300 nm and 550 nm, between 300 nm and 450 nm, between 450 nm and 750 nm, between 450 nm and 650 nm, between 450 nm and 550 nm, between 450 nm and 750 nm, between 450 nm and 650 nm, between 450 nm and 550 nm, between 550 nm and 750 nm, between 550 nm and 650 nm, or between 650 nm and 750 nm. In some embodiments, the photoluminescence spectrum of the core / shell nanostructure has an emission maximum between 500 nm and 550 nm. In some embodiments, the photoluminescence spectrum of the core / shell nanostructure has an emission maximum between 600 nm and 650 nm.
[0172]
[0184] The size distribution of the core / shell nanostructures can be relatively narrow. In some embodiments, the photoluminescence spectrum of the population or the core / shell nanostructures can have a full width at half maximum between 10 nm and 60 nm, between 10 nm and 40 nm, between 10 nm and 30 nm, between 10 nm and 20 nm, between 20 nm and 60 nm, between 20 nm and 40 nm, between 20 nm and 30 nm, between 30 nm and 60 nm, between 30 nm and 40 nm, or between 40 nm and 60 nm. In some embodiments, the photoluminescence spectrum of the population or the core / shell nanostructures can have a full width at half maximum between 35 nm and 45 nm.
[0173]
[0185] In some embodiments, the core / shell nanostructures of the present invention can maintain a high level of photoluminescence intensity for a long time under continuous blue light exposure. In some embodiments, the core / shell nanostructures can maintain 90% intensity (compared to the starting intensity level) for at least 2,000 hours, at least 4,000 hours, at least 6,000 hours, at least 8,000 hours, or at least 10,000 hours. In some embodiments, the core / shell nanostructures can maintain 80% intensity (compared to the starting intensity level) for at least 2,000 hours, at least 4,000 hours, at least 6,000 hours, at least 8,000 hours, or at least 10,000 hours. In some embodiments, the core / shell nanostructures can maintain 70% intensity (compared to the starting intensity level) for at least 2,000 hours, at least 4,000 hours, at least 6,000 hours, at least 8,000 hours, or at least 10,000 hours.
[0174]
[0186] The resulting core / shell nanostructures are optionally embedded in a matrix (e.g., organic polymer, silicon-containing polymer, inorganic, glassy, and / or other matrix) and used to make nanostructured light emitters and / or incorporated into devices such as LEDs, backlights, downlights, or other display or lighting units, or optical filters. Exemplary light emitters and lighting units can generate light of a particular color, for example, by incorporating a population of nanostructures having an emission maximum at or near a desired wavelength, or can generate a wide color gamut by incorporating two or more different populations of nanostructures having different emission maxima. A variety of suitable matrices are known in the art. See, for example, U.S. Pat. No. 7,068,898, as well as U.S. Pat. App. Pub. Nos. 2010 / 0276638, 2007 / 0034833, and 2012 / 0113672. Examples of nanostructured light emitter films, LEDs, backlight units, and the like are described, for example, in U.S. Patent Application Publication No. 2010 / 0276638, U.S. Patent Application Publication No. 2012 / 0113672, U.S. Patent Application Publication No. 2008 / 0237540, U.S. Patent Application Publication No. 2010 / 0110728, and U.S. Patent Application Publication No. 2010 / 0155749, as well as U.S. Patent Nos. 7,374,807, 7,645,397, 6,501,091, and 6,803,719.
[0175]
[0187] The relative molar ratios of InP, ZnSe, and ZnS are calculated based on a spherical InP core of a particular diameter by measuring the volume, mass, and molar amount of the desired spherical shell. For example, a 1.8 nm diameter green InP core coated with 3 monolayers of ZnSe and 4 monolayers of ZnS requires 9.2 molar equivalents of ZnSe and 42.8 molar equivalents of ZnS based on the molar amount of InP bound in the core. This shell structure results in an overall grain size of 6.23 nm. Figure 2 shows a TEM image of a synthetic sample of a 1.8 nm diameter green InP core coated with 3 monolayers of ZnSe and 4 monolayers of ZnS resulting in a measured average grain size of 5.9 nm. Compared to the thin shell material of a previous study with the same type of core with an average grain size of 3.5 nm as shown in Figure 1, it shows that the shell thickness is more than doubled using the method of the present invention. Furthermore, the absorption spectrum of the green InP core in Figure 4 shows a substantial increase in absorbance in the low wavelength region where the ZnSe and ZnSe shell materials are absorbing. Furthermore, the photoluminescence excitation spectra of the core / shell nanostructures follow the same shape, indicating that this additional absorbance is due to the shell material rather than the secondary particle population.
[0176]
[0188] The resulting core / shell nanostructures can be used for imaging or labeling, e.g., biological imaging or labeling. Thus, the resulting core / shell nanostructures are optionally covalently or non-covalently coupled to biomolecules, such as, but not limited to, peptides or proteins (e.g., antibodies or antibody domains, avidin, streptavidin, neutravidin, or other binding or recognition molecules), ligands (e.g., biotin), polynucleotides (e.g., short oligonucleotides or longer nucleic acids), carbohydrates, or lipids (e.g., phospholipids or other micelles). One or more core / shell nanostructures can be coupled to the respective biomolecules as desired for a particular application. Biomolecules labeled with such core / shell nanostructures find use, for example, in vitro, in vivo, and in celluo, e.g., in binding or chemical reaction studies, and in intracellular, cellular, and organism labeling.
[0177]
[0189] The core / shell nanostructures resulting from the above methods are also a feature of the invention. Accordingly, one class of embodiments provides a population of core / shell nanostructures. In some embodiments, the core / shell nanostructures are quantum dots.
[0178] Coating nanostructures with oxide materials
[0190] Regardless of composition, most quantum dots do not maintain their inherently high quantum yield after continuous exposure to excitation photons. Although the use of thick shells has proven effective in mitigating the effects of light-induced quantum yield degradation, photodegradation of quantum dots can be further delayed by covering them with an oxide. Coating quantum dots with an oxide physically isolates their surface from their environment.
[0179]
[0191] Coating quantum dots with oxide materials has been shown to enhance their photostability. In Jo, J.-H., et al., J. Alloys & Compounds 647:6-13 (2015), it was found that overcoating InP / ZnS red-emitting quantum dots with an oxide phase of In2O3 substantially reduced the photodegradation of the quantum dots, as shown by comparative photostability results.
[0180]
[0192] In some embodiments, the nanostructures are coated with an oxide material to enhance stability, hi some embodiments, the oxide material is In2O3, SiO2, Al2O3, or TiO2.
[0181] Quantum dots with increased blue light absorption
[0193] In photoluminescence applications of quantum dots, emission is stimulated by excitation with a more energetic light source. Typically, this is a blue LED with an emission peak in the range of 440 nm to 460 nm. Some quantum dots exhibit relatively low absorbance in this range, which hinders performance, especially in applications where near quantitative conversion of blue photons to quantum dot-emitted photons is desired. One example of such an application is color filters in displays, where leakage of blue light reduces the color gamut range.
[0182]
[0194] Green InP quantum dots absorb less blue light because they also experience an absorption valley in this wavelength range. This valley arises due to quantum confinement. Quantum confinement effects are observed when the size of materials becomes as large as the de Broglie wavelength of the electron wave function. When materials are this small, their electronic and optical properties deviate substantially from those of the bulk material. Quantum confinement breaks down the continuous energy bands of bulk materials, resulting in discrete, atom-like energy levels. Discrete energy states result in a discrete absorption spectrum, which contrasts with the continuous absorption spectrum of bulk semiconductors. Koole, R., “Size Effects on Semiconductor Nanoparticles.” Nanoparticles. Ed. C. de Mello Donega. Heidelberg, Berlin: Springer-Verlag, 2014. Pages 13-50.
[0183]
[0195] Typically, the shell on the quantum dot core is used for passivation and stabilization and is not considered an optically active component. However, the shell on the InP quantum dot core may also participate in the photon conversion process. For example, metal doping is used in CdSe / Cd x Pb 1-x Enhanced optical absorption in S core / shell quantum dots is demonstrated and the increased absorption is attributed to Pb doping. Zhao, H., et al., Small 12:5354-5365 (2016).
[0184]
[0196] CdSe / CdS core / shell quantum dots have been shown to show up to 45-fold reduction in reabsorption when compared to pristine CdSe cores, with quantum dots having thicker shells (~14 monolayers of CdS). I. Coropceanu and MG Bawendi, Nano Lett. 14:4097-4101 (2014).
[0185]
[0197] The photoluminescence excitation spectrum measured at the core emission was found to follow a similar shape to the absorption spectrum, indicating that photons are absorbed at high energy by the shell and the generated excitons can then be transferred to the core with little or no depletion to produce emission. Considering the bulk band gap of ZnSe of 2.7 eV (460 nm), the ZnSe buffer layer can contribute to absorption in the desired range of 440-460 nm. To exploit this insight, quantum dots with a thicker ZnSe buffer were synthesized and found to have even stronger absorbance in the wavelength range of 440-460 nm, as shown in Figure 10.
[0186]
[0198] In some embodiments, the absorption spectrum of the nanostructures can be measured using a UV-Vis spectrophotometer.
[0187]
[0199] If a nanostructure absorbs light at a wavelength between about 440 nm and about 495 nm, it absorbs blue light. In some embodiments, the blue light absorption of the nanostructure is measured at a wavelength between about 440 nm and about 495 nm, between about 440 nm and about 480 nm, between about 440 nm and about 460 nm, between about 440 nm and about 450 nm, between about 450 nm and about 495 nm, between about 450 nm and about 480 nm, between about 450 nm and about 460 nm, between about 460 nm and about 495 nm, between about 460 nm and about 480 nm, or between about 480 nm and about 495 nm. In some embodiments, the blue light absorption of the nanostructure is measured at a wavelength of 440 nm, 450 nm, 460 nm, 480 nm, or 495 nm.
[0188]
[0200] UV-Vis spectroscopy or UV-Vis spectrophotometry measures light in the visible and nearby (near ultraviolet and near infrared) ranges. In this region of the electromagnetic spectrum, electronic transitions of molecules occur. UV-Vis spectroscopy is based on absorbance. In spectroscopy, absorbance A is: A λ =log 10 (I0 / I) where I is the intensity of light at a specified wavelength λ that has been transmitted through the sample (transmitted light intensity) and I0 is the intensity of the light before it enters the sample, i.e., the incident light. The term absorption refers to the physical process of absorbing light, while absorbance refers to a mathematical quantity. Absorbance has no true units, but is often reported in "absorbance units," or AU.
[0189]
[0201] Optical density (OD) is the absorbance per unit length, i.e., the absorbance divided by the thickness of the sample. The optical density at wavelength λ is: O.D. λ =A λ / ι=-(1 / ι)log 10 (I0 / I) is defined as: ι = the distance traveled by light through the sample in cm (sample thickness); A λ = absorbance at wavelength λ; I0 = intensity of the incident light beam; and I = Intensity of the transmitted light beam Optical density is measured in units of ODU, which is equal to AU / cm. For a sample thickness of 1 cm, OD λ =A λ It is.
[0190]
[0202] In order to compare UV-vis spectral measurements, the absorbance measurements need to be normalized. Absorption spectra are normalized by dividing each absorbance curve by their respective absorbance at a specific wavelength. Generally, the absorbance at the first exciton peak absorption wavelength is chosen as the normalization point.
[0191]
[0203] To normalize the optical density at a desired wavelength, the formula: Normalized OD λ =OD λ / Peak ratio = A λ / (Peak ratio * I) The ratio of optical densities at a desired wavelength can be compared to the optical density at the first exciton peak absorption wavelength using the formula: O.D. λ = optical density of a sample measured at a certain wavelength; Peak ratio = optical density at the first exciton peak absorption wavelength; A λ = absorbance of a sample measured at a wavelength; and ι = the distance light travels through the sample in cm (sample thickness) For example, the normalized optical density at 450 nm is given by the formula: Normalized OD 450 =OD 450 / Peak ratio = A 450 / (Peak ratio * I) can be calculated using the formula: O.D. 450 = optical density of the sample measured at 450 nm; A 450 = absorbance of the sample measured at 450 nm; Peak Ratio = Optical Density at the first exciton peak absorption wavelength; and ι = the distance light travels through the sample in cm (sample thickness) It is.
[0192]
[0204] In some embodiments, the nanostructures have a wavelength between about 1.0 and about 8.0, between about 1.0 and about 6.0, between about 1.0 and about 3.0, between about 1.0 and about 2.0, between about 1.0 and about 1.8, between about 1.0 and about 1.5, between about 1.5 and about 8.0, between about 1.5 and about 6.0, between about 1.5 and about 3.0, between about 1.5 and about 1.5 having a normalized optical density of between about 2.0, between about 1.5 and about 1.8, between about 1.8 and about 8.0, between about 1.8 and about 6.0, between about 1.8 and about 3.0, between about 1.8 and about 2.0, between about 2.0 and about 8.0, between about 2.0 and about 6.0, between about 2.0 and about 3.0, between about 3.0 and about 8.0, between about 3.0 and about 6.0, or between about 6.0 and about 8.0. In some embodiments, the nanostructures of the present invention have a spectral response of between about 1.0 and about 8.0, between about 1.0 and about 6.0, between about 1.0 and about 3.0, between about 1.0 and about 2.0, between about 1.0 and about 1.8, between about 1.0 and about 1.5, between about 1.5 and about 8.0, between about 1.5 and about 6.0, between about 1.5 and about 3.0, between about 1. and / or has a normalized optical density of between about 1.5 and about 2.0, between about 1.5 and about 1.8, between about 1.8 and about 8.0, between about 1.8 and about 6.0, between about 1.8 and about 3.0, between about 1.8 and about 2.0, between about 2.0 and about 8.0, between about 2.0 and about 6.0, between about 2.0 and about 3.0, between about 3.0 and about 8.0, between about 3.0 and about 6.0, or between about 6.0 and about 8.0. In some embodiments, the nanostructures have a refractive index of between about 1.0 and about 8.0, between about 1.0 and about 6.0, between about 1.0 and about 3.0, between about 1.0 and about 2.0, between about 1.0 and about 1.8, between about 1.0 and about 1.5, between about 1.5 and about 8.0, between about 1.5 and about 6.0, between about 1.5 and about 3.0, between about 1.5 and about 2.0 at a wavelength of about 450 nm. between about 1.5 and about 1.8, between about 1.8 and about 8.0, between about 1.8 and about 6.0, between about 1.8 and about 3.0, between about 1.8 and about 2.0, between about 2.0 and about 8.0, between about 2.0 and about 6.0, between about 2.0 and about 3.0, between about 3.0 and about 8.0, between about 3.0 and about 6.0, or between about 6.0 and about 8.0. In some embodiments, a method of increasing the blue light normalized absorbance of a population of nanostructures is provided.In some embodiments, the present invention provides methods for increasing the blue light normalized optical density of a population of nanostructures.
[0193]
[0205] In some embodiments, the blue light normalized optical density is increased by increasing the number of shell monolayers. In some embodiments, a shell containing about 2 monolayers exhibits an increased blue light normalized optical density compared to a shell containing between about 0.25 and about 1 monolayer. In some embodiments, a shell containing 3 monolayers exhibits an increased blue light normalized optical density compared to a shell containing between about 0.25 and about 2 monolayers, between about 0.25 and about 1 monolayer, or between about 1 and about 2 monolayers. In some embodiments, a shell containing 4 monolayers exhibits an increased blue light normalized optical density compared to a shell containing between about 0.25 and about 3 monolayers, between about 0.25 and about 2 monolayers, between about 0.25 and about 1 monolayer, between about 1 and about 3 monolayers, or between about 1 and about 2 monolayers. In some embodiments, a shell comprising 5 monolayers exhibits increased blue light normalized optical density as compared to a shell comprising between about 0.25 and about 4 monolayers, between about 0.25 and about 3 monolayers, between about 0.25 and about 2 monolayers, between about 0.25 and about 1 monolayer, between about 1 and about 4 monolayers, between about 1 and about 3 monolayers, between about 1 and about 2 monolayers, between about 2 and about 4 monolayers, between about 2 and about 3 monolayers, or between about 3 and about 4 monolayers. In some embodiments, a shell comprising 6 monolayers exhibits increased blue light normalized optical density as compared to a shell comprising between about 0.25 to about 5 monolayers, between about 0.25 to about 4 monolayers, between about 0.25 to about 3 monolayers, between about 0.25 to about 2 monolayers, between about 0.25 to about 1 monolayer, between about 1 to about 5 monolayers, between about 1 to about 4 monolayers, between about 1 to about 3 monolayers, between about 1 to about 2 monolayers, between about 2 to about 5 monolayers, between about 2 to about 4 monolayers, between about 2 to about 3 monolayers, between about 3 to about 5 monolayers, between about 3 to about 4 monolayers, or between about 4 to about 5 monolayers. In some embodiments, a shell that includes 7 monolayers may include between about 0.25 and about 6 monolayers, between about 0.25 and about 5 monolayers, between about 0.25 and about 4 monolayers, between about 0.25 and about 3 monolayers, between about 0.25 and about 2 monolayers, between about 0.25 and about 1 monolayer, between about 1 and about 6 monolayers, The shells exhibit increased blue light normalized optical density compared to shells including between about 1 and about 5 monolayers, between about 1 and about 4 monolayers, between about 1 and about 3 monolayers, between about 1 and about 2 monolayers, between about 2 and about 6 monolayers, between about 2 and about 5 monolayers, between about 2 and about 4 monolayers, between about 2 and about 3 monolayers, between about 3 and about 6 monolayers, between about 3 and about 5 monolayers, between about 3 and about 4 monolayers, between about 4 and about 6 monolayers, between about 4 and about 5 monolayers, or between about 5 and about 6 monolayers. In some embodiments, a shell comprising 8 monolayers may comprise between about 0.25 and about 7 monolayers, between about 0.25 and about 6 monolayers, between about 0.25 and about 5 monolayers, between about 0.25 and about 4 monolayers, between about 0.25 and about 3 monolayers, between about 0.25 and about 2 monolayers, between about 0.25 and about 1 monolayer, between about 1 and about 7 monolayers, between about 1 and about 6 monolayers, between about 1 and about 5 monolayers, between about 1 and about 4 monolayers, between about 1 and about 3 monolayers, between about 1 and about 2 monolayers, between about 2 and about 7 monolayers, a monolayer of about 2 to about 6 monolayers, about 2 to about 5 monolayers, about 2 to about 4 monolayers, about 2 to about 3 monolayers, about 3 to about 7 monolayers, about 3 to about 6 monolayers, about 3 to about 5 monolayers, about 3 to about 4 monolayers, about 4 to about 7 monolayers, about 4 to about 6 monolayers, about 4 to about 5 monolayers, about 5 to about 7 monolayers, about 5 to about 6 monolayers, or about 6 to about 7 monolayers.
[0194]
[0206] In some embodiments, as the number of shell monolayers increases, the normalized optical density increases from about 0.1 to about 2.0, from about 0.1 to about 1.5, from about 0.1 to about 1.0, from about 0.1 to about 0.5, from about 0.1 to about 0.3, from about 0.3 to about 2.0, from about 0.3 to about 1.5, from about 0.3 to about 1.0, from about 0.3 to about 0.5, from about 0.5 to about 2.0, from about 0.5 to about 1.5, from about 0.5 to about 1.0, from about 1.0 to about 2.0, from about 1.0 to about 1.5, or from about 1.5 to about 2.0. In some embodiments, as the number of shell monolayers increases, the optical density at wavelengths between about 440 nm and about 460 nm increases by between about 0.1 and about 2.0, between about 0.1 and about 1.5, between about 0.1 and about 1.0, between about 0.1 and about 0.5, between about 0.1 and about 0.3, between about 0.3 and about 2.0, between about 0.3 and about 1.5, between about 0.3 and about 1.0, between about 0.3 and about 0.5, between about 0.5 and about 2.0, between about 0.5 and about 1.5, between about 0.5 and about 1.0, between about 1.0 and about 2.0, between about 1.0 and about 1.5, or between about 1.5 and about 2.0. In some embodiments, as the number of shell monolayers increases, the optical density at a wavelength of about 450 nm increases by between about 0.1 and about 2.0, between about 0.1 and about 1.5, between about 0.1 and about 1.0, between about 0.1 and about 0.5, between about 0.1 and about 0.3, between about 0.3 and about 2.0, between about 0.3 and about 1.5, between about 0.3 and about 1.0, between about 0.3 and about 0.5, between about 0.5 and about 2.0, between about 0.5 and about 1.5, between about 0.5 and about 1.0, between about 1.0 and about 2.0, between about 1.0 and about 1.5, or between about 1.5 and about 2.0.
[0195]
[0207] In some embodiments, increasing the number of ZnSe shell monolayers increases the blue light normalized optical density. In some embodiments, increasing the number of ZnSe shell monolayers increases the normalized optical density at wavelengths between about 440 nm and about 460 nm. In some embodiments, increasing the number of ZnSe shell monolayers increases the normalized optical density at a wavelength of about 450 nm.
[0196]
[0208] In some embodiments, as the number of monolayers of ZnSe shells increases, the blue light normalized optical density increases from about 0.1 to about 2.0, from about 0.1 to about 1.5, from about 0.1 to about 1.0, from about 0.1 to about 0.5, from about 0.1 to about 0.3, from about 0.3 to about 2.0, from about 0.3 to about 1.5, from about 0.3 to about 1.0, from about 0.3 to about 0.5, from about 0.5 to about 2.0, from about 0.5 to about 1.5, from about 0.5 to about 1.0, from about 1.0 to about 2.0, from about 1.0 to about 1.5, or from about 1.5 to about 2.0. In some embodiments, as the number of monolayers of the ZnSe shell increases, the optical density at wavelengths between about 440 nm and about 460 nm increases by between about 0.1 and about 2.0, between about 0.1 and about 1.5, between about 0.1 and about 1.0, between about 0.1 and about 0.5, between about 0.1 and about 0.3, between about 0.3 and about 2.0, between about 0.3 and about 1.5, between about 0.3 and about 1.0, between about 0.3 and about 0.5, between about 0.5 and about 2.0, between about 0.5 and about 1.5, between about 0.5 and about 1.0, between about 1.0 and about 2.0, between about 1.0 and about 1.5, or between about 1.5 and about 2.0. In some embodiments, as the number of monolayers of ZnSe shell increases, the optical density at a wavelength of about 450 nm increases by between about 0.1 and about 2.0, between about 0.1 and about 1.5, between about 0.1 and about 1.0, between about 0.1 and about 0.5, between about 0.1 and about 0.3, between about 0.3 and about 2.0, between about 0.3 and about 1.5, between about 0.3 and about 1.0, between about 0.3 and about 0.5, between about 0.5 and about 2.0, between about 0.5 and about 1.5, between about 0.5 and about 1.0, between about 1.0 and about 2.0, between about 1.0 and about 1.5, or between about 1.5 and about 2.0.
[0197]
[0209] A band gap is the range in a solid over which electronic states cannot exist. By controlling the composition of an alloy or constructing layered nanostructures with alternating compositions, the band gap and resulting wavelength of the nanostructure can be controlled or varied.
[0198]
[0210] The wavelength of the nanocrystals is given by the following formula: Wavelength (unit: nm) = 1240.8 / Energy (unit: eV) can be calculated from the bulk band gap by
[0199]
[0211] Thus, ZnSe nanocrystals with a bulk bandgap of 2.7 eV correspond to a wavelength of about 460 nm, ZnS nanocrystals with a bulk bandgap of 3.6 eV correspond to a wavelength of about 345 nm, and ZnTe nanocrystals with a bulk bandgap of 2.25 eV correspond to a wavelength of about 551 nm.
[0200]
[0212] To increase the optical density at 450 nm, ZnSe can be alloyed with at least one component having a larger bandgap, such as ZnS or GaN, and to increase the optical density at 480 nm, ZnSe can be alloyed with at least one component having a smaller bandgap, such as AlP, CdS, GaP, ZnTe, AlAs, CdSe, AlSb, CdTe, GaAs, or InP.
[0201]
[0213] To increase the optical density at 450 nm, ZnS can be alloyed with at least one component having a smaller bandgap, such as ZnSe, AlP, CdS, GaP, ZnTe, AlAs, CdSe, AlSb, CdTe, GaAs, or InP, and to increase the optical density at 450 nm, ZnTe can be alloyed with at least one component having a larger bandgap, such as ZnS or GaN.
[0202]
[0214] In some embodiments, the components added to form the alloy are selected from the group consisting of ZnS, GaN, ZnSe, AlP, CdS, GaP, ZnTe, AlAs, CdSe, AlSb, CdTe, GaAs, Sn, Ge, and InP.
[0203]
[0215] In some embodiments, the band gap and resulting wavelength of the nanostructure is controlled by adding a component to at least one shell monolayer to form an alloy. In some embodiments, the component is added to between about 0.25 and about 8 monolayers, between about 0.25 and about 6 monolayers, between about 0.25 and about 4 monolayers, between about 0.25 and about 2 monolayers, between about 0.25 and about 1 monolayer, between about 1 and about 8 monolayers, between about 1 and about 6 monolayers, between about 1 and about 4 monolayers, between about 1 and about 2 monolayers, between about 2 and about 8 monolayers, between about 2 and about 6 monolayers, between about 2 and about 4 monolayers, between about 4 and about 8 monolayers, between about 4 and about 6 monolayers, or between about 6 and about 8 monolayers to form an alloy.
[0204]
[0216] In some embodiments, the alloy formed increases the normalized optical density of the nanostructure at a particular wavelength. In some embodiments, the alloy formed increases the blue normalized optical density of the nanostructure. In some embodiments, the alloy formed increases the normalized optical density of the nanostructure between about 440 nm and about 460 nm. In some embodiments, the alloy formed increases the normalized optical density of the nanostructure at about 450 nm.
[0205]
[0217] In some embodiments, the addition of at least one component to form an alloy increases the blue light normalized optical density by between about 0.1 and about 2.0, between about 0.1 and about 1.5, between about 0.1 and about 1.0, between about 0.1 and about 0.5, between about 0.1 and about 0.3, between about 0.3 and about 2.0, between about 0.3 and about 1.5, between about 0.3 and about 1.0, between about 0.3 and about 0.5, between about 0.5 and about 2.0, between about 0.5 and about 1.5, between about 0.5 and about 1.0, between about 1.0 and about 2.0, between about 1.0 and about 1.5, or between about 1.5 and about 2.0. In some embodiments, the addition of at least one component to form an alloy increases the optical density at wavelengths between about 440 nm and about 460 nm by between about 0.1 and about 2.0, between about 0.1 and about 1.5, between about 0.1 and about 1.0, between about 0.1 and about 0.5, between about 0.1 and about 0.3, between about 0.3 and about 2.0, between about 0.3 and about 1.5, between about 0.3 and about 1.0, between about 0.3 and about 0.5, between about 0.5 and about 2.0, between about 0.5 and about 1.5, between about 0.5 and about 1.0, between about 1.0 and about 2.0, between about 1.0 and about 1.5, or between about 1.5 and about 2.0. In some embodiments, the addition of at least one component to form an alloy increases the optical density at a wavelength of about 450 nm by between about 0.1 and about 2.0, between about 0.1 and about 1.5, between about 0.1 and about 1.0, between about 0.1 and about 0.5, between about 0.1 and about 0.3, between about 0.3 and about 2.0, between about 0.3 and about 1.5, between about 0.3 and about 1.0, between about 0.3 and about 0.5, between about 0.5 and about 2.0, between about 0.5 and about 1.5, between about 0.5 and about 1.0, between about 1.0 and about 2.0, between about 1.0 and about 1.5, or between about 1.5 and about 2.0.
[0206] Nanostructured Compositions
[0218] In some embodiments, the present disclosure provides a nanostructure composition comprising at least one population of nanostructures, wherein the nanostructures are multi-layered nanostructures comprising a core and at least two shells, wherein the at least two shells comprise different shell materials.
[0207]
[0219] In some embodiments, the thickness of at least one shell is between 0.7 nm and 3.5 nm.
[0208]
[0220] In some embodiments, the nanostructure composition further comprises a solvent.
[0209]
[0221] In some embodiments, the nanostructures are quantum dots.
[0210] Nanostructured Layer
[0222] In some embodiments, the present disclosure provides a nanostructured layer comprising at least one population of nanostructures, wherein the nanostructures are multi-layered nanostructures comprising a core and at least two shells, wherein the at least two shells comprise different shell materials.
[0211]
[0223] In some embodiments, the thickness of at least one shell is between 0.7 nm and 3.5 nm.
[0212]
[0224] In some embodiments, the nanostructures are quantum dots.
[0213] Nanostructured Molded Articles
[0225] In some embodiments, the present disclosure provides a nanostructured molded article comprising at least one population of nanostructures, wherein the nanostructures are multi-layered nanostructures comprising a core and at least two shells, wherein the at least two shells comprise different shell materials.
[0214]
[0226] In some embodiments, the thickness of at least one shell is between 0.7 nm and 3.5 nm.
[0215]
[0227] In some embodiments, the shaped article is a film, a substrate for a display, or a light emitting diode.
[0216]
[0228] In some embodiments, the nanostructures are quantum dots.
[0217]
[0229] In some embodiments, the present disclosure provides: (a) a first barrier layer; (b) a second barrier layer; (c) a nanostructured layer between a first barrier layer and a second barrier layer, wherein the nanostructure is a multilayer nanostructure comprising a core and at least two shells, the at least two shells comprising different shell materials.
[0218]
[0230] In some embodiments, the thickness of at least one shell is between 0.7 nm and 3.5 nm.
[0219]
[0231] In some embodiments, the nanostructures are quantum dots.
[0220] Fabrication of nanostructured layers
[0232] In some embodiments, the nanostructure layer can be embedded in. As used herein, the term "embedded" is used to indicate that the nanostructure population is surrounded or enveloped by the polymer that constitutes the majority of the matrix's components. In some embodiments, the at least one nanostructure population is suitably uniformly distributed throughout the matrix. In some embodiments, the at least one nanostructure population is distributed according to an application specific distribution. In some embodiments, the nanostructures are mixed into the polymer and applied to the surface of the substrate.
[0221]
[0233] In some embodiments, the nanostructure composition is deposited to form a nanostructure layer. In some embodiments, the nanostructure composition can be deposited by any suitable method known in the art, including, but not limited to, painting, spray coating, solvent spraying, wet coating, adhesive coating, spin coating, tape coating, roll coating, flow coating, inkjet vapor jetting, drop casting, blade coating, mist deposition, or combinations thereof. The nanostructure composition can be coated directly onto the desired layer of the substrate. Alternatively, a solid layer can be formed from the nanostructure composition as a separate element and subsequently attached to the substrate. In some embodiments, the nanostructure composition can be deposited onto one or more barrier layers.
[0222]
[0234] In some embodiments, the nanostructured layer is cured after deposition. Suitable curing methods include photocuring, such as UV curing, and thermal curing. Conventional film-by-film processing, tape coating, and / or roll-to-roll manufacturing methods can be used to form the nanostructured layer.
[0223] Spin coating
[0235] In some embodiments, the nanostructure composition is deposited on the substrate using spin coating. In spin coating, a small amount of material is typically placed on the center of a substrate mounted on a machine called a spinner, which is held in place by a vacuum. The spinner causes the substrate to spin at high speed, which creates a centripetal force that spreads the material from the center to the edge of the substrate. Most of the material is shaken off, but some remains on the substrate and, as the spinning continues, a thin film of material is formed on the surface. The final thickness of the film is determined by the nature of the material and the substrate being deposited, as well as the parameters selected for the spin process, such as spin speed, acceleration, and spin time. In some embodiments, spin speeds of about 1500 rpm to about 6000 rpm are used, with spin times of about 10 to 60 seconds.
[0224] Mist accumulation
[0236] In some embodiments, the nanostructure composition is deposited on the substrate using mist deposition. Mist deposition is performed at room temperature and atmospheric pressure, and film thickness can be precisely controlled by varying the process conditions. During mist deposition, liquid source material is transformed into a very fine mist by nitrogen gas and delivered to the deposition chamber. The mist is then attracted to the wafer surface by a high voltage potential between a field screen and a wafer holder. After the droplets coalesce on the wafer surface, the wafer can be removed from the chamber and thermally cured to evaporate the solvent. The liquid precursor is a mixture of solvent and material to be deposited. It is delivered to the atomizer by pressurized nitrogen gas. Price, SC, et al., “Formation of Ultra-Thin Quantum Dot Films by Mist Deposition,” ESC Transactions 11:89-94 (2007).
[0225] Spray Coating
[0237] In some embodiments, the nanostructure composition is deposited on the substrate using spray coating. A typical equipment for spray coating includes a spray nozzle, a sprayer, a precursor solution, and a carrier gas. In the spray deposition process, the precursor solution is atomized into micro-sized droplets by a carrier gas or by atomization (e.g., ultrasonic, air blast, or electrostatic). The droplets exiting the sprayer are accelerated near the substrate surface through a nozzle using a carrier gas that is controlled and regulated as desired. The relative motion between the spray nozzle and the substrate is dictated by design to completely cover the substrate.
[0226]
[0238] In some embodiments, the application of the nanostructure composition further comprises a solvent. In some embodiments, the solvent for applying the nanostructure composition is water, an organic solvent, an inorganic solvent, a halogenated organic solvent, or a mixture thereof. Illustrative solvents include, but are not limited to, water, DO, acetone, ethanol, dioxane, ethyl acetate, methyl ethyl ketone, isopropanol, anisole, γ-butyrolactone, dimethylformamide, N-methylpyrroldinone, dimethylacetamide, hexamethylphosphoramide, toluene, dimethylsulfoxide, cyclopentanone, tetramethylene sulfoxide, xylene, ε-caprolactone, tetrahydrofuran, tetrachloroethylene, chloroform, chlorobenzene, dichloromethane, 1,2-dichloroethane, 1,1,2,2-tetrachloroethane, or a mixture thereof.
[0227]
[0239] In some embodiments, the nanostructure composition is thermally cured to form the nanostructured layer. In some embodiments, the composition is cured using UV light. In some embodiments, the nanostructure composition is coated directly onto the barrier layer of the nanostructured film, and then an additional barrier layer is deposited onto the nanostructured layer to form the nanostructured film. A support substrate can be used under the barrier film to provide strength, stability, and coating uniformity, and to prevent material inconsistencies, bubble formation, and wrinkling or folding of the barrier layer material or other materials. In addition, one or more barrier layers are preferably deposited on the nanostructured layer to encapsulate the material between the top and bottom barrier layers. Suitably, the barrier layers can be stacked as a laminate film, optionally sealed or further processed, and the nanostructured film can then be incorporated into a separate light-emitting device. The deposition method of the nanostructure composition can include additional or different components, as will be understood by those skilled in the art. Such embodiments allow for in-line process tuning of the nanostructured emission properties, such as brightness and color (e.g., to adjust the white point of the quantum dot film), as well as the film thickness of the nanostructures, and other properties. Additionally, these embodiments allow for periodic testing of the nanostructured film properties during production, and any necessary toggling to achieve precise nanostructured film properties. Because a computer program can be used to electronically vary the amounts of each of the mixtures used to form the nanostructured film, such testing and adjustments can also be achieved without modifying the mechanical configuration of the processing line.
[0228] Barrier Layer
[0240] In some embodiments, the molded article includes one or more barrier layers disposed on one or both sides of the nanostructured layer. A suitable barrier layer protects the nanostructured layer and the molded article from environmental conditions such as high temperature, oxygen, and moisture. Suitable barrier materials include non-yellowing transparent optical materials that are hydrophobic, chemically and mechanically compatible with the molded article, exhibit light and chemical stability, and can withstand high temperatures. In some embodiments, the one or more barrier layers are index matched to the molded article. In some embodiments, the matrix material of the molded article and one or more adjacent barrier layers are index matched to have approximately the same index of refraction, such that a large portion of the light passing through the barrier layer toward the molded article is transmitted from the barrier layer into the nanostructured layer. This index matching reduces optical losses at the interface between the barrier and the matrix material.
[0229]
[0241] The barrier layer is suitably a solid material and may be a hardened liquid, gel, or polymer. The barrier layer may comprise a flexible or non-flexible material depending on the particular application. The barrier layer is preferably a planar layer and may comprise any suitable shape and surface area form depending on the particular light emitting application. In some embodiments, one or more barrier layers are compatible with laminate film processing techniques, whereby a nanostructured layer is disposed on at least one first barrier layer and at least one second barrier layer is disposed on the nanostructured layer opposite the nanostructured layer to form a molded article according to an embodiment. Suitable barrier materials include any suitable barrier material known in the art. In some embodiments, suitable barrier materials include glass, polymers, and oxides. Suitable barrier layer materials include, but are not limited to, polymers, such as polyethylene terephthalate (PET); oxides, such as silicon oxide, titanium oxide, or aluminum oxide (e.g., SiO2, SiO3, TiO2, or Al2O3); and suitable combinations thereof. Preferably, each barrier layer of the molded article comprises at least two layers comprising different materials or compositions, the multi-layer barriers eliminating or reducing pinhole defect alignment in the barrier layers and providing an effective barrier to oxygen and moisture permeating into the nanostructured layer. The nanostructured layer may comprise any suitable material or combination of materials and may comprise any suitable number of barrier layers on either or both sides of the nanostructured layer. The material, thickness, and number of barrier layers are determined by the particular application and are appropriately selected to maximize the barrier protection and brightness of the nanostructured layer while minimizing the thickness of the molded article. In a preferred embodiment, each barrier layer comprises a laminate film, preferably a bi-laminate film, and the thickness of each barrier layer is thick enough to minimize wrinkling during roll-to-roll or laminate manufacturing processes. The number or thickness of the barriers may be further driven by regulatory toxicity guidelines in embodiments where the nanostructures comprise heavy metals or other toxic materials, which may require more or thicker barrier layers. Additional considerations regarding the barriers include cost, availability, and mechanical strength.
[0230]
[0242] In some embodiments, the nanostructured film comprises two or more barrier layers adjacent to each side of the nanostructured layer, e.g., two or three layers on each side of the nanostructured layer, or two barrier layers on each side, hi some embodiments, each barrier layer comprises a thin glass sheet, e.g., a glass sheet having a thickness of about 100 μm, 100 μm or less, or 50 μm or less.
[0231]
[0243] Each barrier layer of the nanostructured molded article can have any suitable thickness, which is determined by the light emitting device and application, as well as the individual requirements and properties of the individual film components, such as the barrier layer and the nanostructured layer, as will be understood by those skilled in the art. In some embodiments, each barrier layer can have a thickness of 50 μm or less, 40 μm or less, 30 μm or less, 25 μm or less, 20 μm or less, or 15 μm or less. In some embodiments, the barrier layer includes an oxide coating that can include materials such as silicon oxide, titanium oxide, and aluminum oxide (e.g., SiO2, SiO3, TiO2, or Al2O3). The oxide coating can have a thickness of about 10 μm or less, 5 μm or less, 1 μm or less, or 100 nm or less. In some embodiments, the barrier includes a thin oxide coating having a thickness of about 100 nm or less, 10 nm or less, 5 nm or less, or 3 nm or less. The top and / or bottom barrier can consist of a thin oxide coating, or can include a thin oxide coating and one or more additional layers of material.
[0232] Nanostructured Layer Features and Embodiments
[0244] In some embodiments, the nanostructured layer is used to form a display device.As used herein, display device refers to any system that has an emissive display.Such devices include, but are not limited to, devices that include liquid crystal displays, televisions, computers, mobile phones, smartphones, personal digital assistants (PDAs), gaming devices, e-readers, digital cameras, etc.
[0233] Molded Articles with Increased External Quantum Efficiency (EQE)
[0245] Light-emitting diodes (LEDs) made with CdSe-based red quantum dots have been reported to have an EQE of over 20%, which is close to the theoretical limit of efficiency for quantum dot LEDs. In contrast, LEDs made with InP-based quantum dots have only been reported to exhibit an EQE of 2.3% for the red quantum dots and 3.5% for the green quantum dots. This difference is believed to be due, in part, to the quenching that InP quantum dots exhibit when deposited in dense films.
[0234]
[0246] Similarly, InP red quantum dots exhibit solution quantum yields as high as 90%, similar to the maximum quantum yields exhibited by CdSe quantum dots, but spin-coated InP red quantum dots exhibit solid-state quantum yields of 20%. In comparison, CdSe films formed using similar techniques exhibit solid-state quantum yields of 60-70%.
[0235]
[0247] In some embodiments, molded articles made using the nanostructures described herein exhibit an EQE of between about 6% and about 20%, between about 6% and about 15%, between about 6% and about 12%, between about 6% and about 10%, between about 6% and about 8%, between about 6% and about 7%, between about 7% and about 20%, between about 7% and about 15%, between about 7% and about 12%, between about 7% and about 10%, between about 7% and about 8%, between about 8% and about 20%, between about 8% and about 15%, between about 8% and about 12%, between about 8% and about 10%, between about 10% and about 20%, between about 10% and about 15%, between about 10% and about 12%, between about 12% and about 20%, between about 12% and about 15%, or between about 15% and about 20%. In some embodiments, the nanostructures are quantum dots. In some embodiments, the molded article is a light emitting diode.
[0236]
[0248] In some embodiments, molded articles produced by increasing the number of ZnSe shell monolayers in the nanostructure layer have an increased EQE. In some embodiments, increasing the number of ZnSe shell monolayers in the nanostructure by one monolayer increases the EQE of the molded article by about 0.5% to about 3%, between about 0.5% to about 2%, between about 0.5% to about 1%, between about 1% to about 3%, between about 1% to about 2%, or between about 2% to about 3%. In some embodiments, increasing the number of ZnSe shell monolayers in the nanostructure by two monolayers increases the EQE of the molded article by about 0.5% to about 4%, between about 0.5% to about 3%, between about 0.5% to about 2%, between about 0.5% to about 1%, between about 1% to about 4%, between about 1% to about 3%, between about 1% to about 2%, or between about 2% to about 3%. In some embodiments, the nanostructures are quantum dots. In some embodiments, the molded article is a light emitting diode.
[0237]
[0249] In some embodiments, molded articles made with increasing numbers of ZnSe shell monolayers in the nanostructures have increased luminance at a voltage of 7 V. In some embodiments, molded articles made using a population of nanostructures described herein have a luminance of about 3000 cd / m 2 ~about 6000cd / m 2 Approximately 3000cd / m 2 ~about 5000cd / m 2 Approximately 3000cd / m 2 ~about 4000cd / m 2 Approximately 3000cd / m 2 ~About 3500cd / m 2 Approximately 3500cd / m 2 ~about 6000cd / m 2 Approximately 3500cd / m 2 ~about 5000cd / m 2 Approximately 3500cd / m 2 ~about 4000cd / m 2 Approximately 4000cd / m 2 ~about 6000cd / m 2 Approximately 4000cd / m 2 ~about 5000cd / m 2 or about 5000 cd / m 2 ~about 6000cd / m 2At 7V it has a brightness between 0.01 and 0.1.
[0238]
[0250] In some embodiments, molded articles made with increasing numbers of ZnSe shell monolayers in the nanostructures exhibit increased brightness at a voltage of 7V. In some embodiments, increasing the number of monolayers of ZnSe shells in the nanostructure by one monolayer increases the luminance at 7 V by between about 5% and about 35%, between about 5% and about 25%, between about 5% and about 20%, between about 5% and about 15%, between about 5% and about 10%, between about 10% and about 35%, between about 10% and about 30%, between about 10% and about 25%, between about 10% and about 20%, between about 10% and about 15%, between about 15% and about 35%, between about 15% and about 30%, between about 15% and about 25%, between about 15% and about 20%, between about 20% and about 35%, between about 20% and about 30%, between about 20% and about 25%, between about 25% and about 35%, between about 25% and about 30%, or between about 30% and about 35%. In some embodiments, increasing the number of ZnSe shell monolayers in the nanostructure by 2 monolayers increases the luminance at 7 V by between about 15% and about 50%, between about 15% and about 45%, between about 15% and about 40%, between about 15% and about 35%, between about 15% and about 30%, between about 20% and about 50%, between about 20% and about 45%, between about 20% and about 40%, between about 20% and about 35%, between about 20% and about 30%, between about 20% to about 25%, between about 20% to about 30%, between about 25% to about 50%, between about 25% to about 45%, between about 20% to about 40%, between about 30% to about 50%, between about 30% to about 45%, between about 35% to about 50%, between about 35% to about 45%, between about 35% to about 40%, between about 40% to about 50%, between about 40% to about 45%, or between about 45% to about 50%. In some embodiments, the nanostructures are quantum dots. In some embodiments, the molded article is a light emitting diode.
[0239]
[0251] In some embodiments, molded articles made using the nanostructures described herein have a viscosity of between about 10% and about 50%, between about 10% and about 45%, between about 10% and about 40%, between about 10% and about 35%, between about 10% and about 30%, between about 10% and about 20%, between about 20% and about 50%, between about 20% and about 45%, between about 20% and about 4 ...50%, between about 20% and about The solid quantum yield may be between about 35%, between about 20% and about 30%, between about 30% and about 50%, between about 30% and about 45%, between about 30% and about 40%, between about 30% and about 35%, between about 35% and about 50%, between about 35% and about 45%, between about 35% and about 40%, between about 40% and about 50%, between about 40% and about 45%, or between about 45% and about 50%. In some embodiments, the nanostructures are quantum dots. In some embodiments, the molded article is a light emitting diode.
[0240]
[0252] In some embodiments, films made with increasing the number of ZnSe shell monolayers in the nanostructures have increased film quantum yields. In some embodiments, increasing the number of ZnSe shell monolayers in the nanostructures by one monolayer increases the film quantum yield by about 3% and about 10%, about 3% and about 8%, about 3% and about 6%, about 3% and about 5%, about 3% and about 4%, about 4% and about 10%, about 4% and about 8%, about 4% and about 6%, about 4% and about 5%, about 5% and about 10%, about 5% and about 8%, about 5% and about 6%, about 6% and about 10%, about 6% and about 8%, or about 8% and about 10%. In some embodiments, increasing the number of monolayers of ZnSe shells in the nanostructure by two monolayers increases the film quantum yield by about 6% and about 20%, about 6% and about 15%, about 6% and about 12%, about 6% and about 10%, about 6% and about 8%, about 6% and about 7%, about 7% and about 20%, about 7% and about 15%, about 7% and about 12%, about 7% and about 10%, about 7% and about 8%, about 8% and about 20%, about 8% and about 15%, about 8% and about 12%, about 8% and about 10%, about 10% and about 20%, about 10% and about 15%, about 10% and about 12%, about 12% and about 20%, about 12% and about 15%, or about 15% and about 20%. EXAMPLES
[0241]
[0253] The following examples are illustrative, but not limiting, of the products and methods described herein. Suitable modifications and adaptations of the variety of conditions, formulations, and other parameters normally encountered in the art and obvious to those skilled in the art in light of this disclosure are within the spirit and scope of the invention.
[0242]
[0254] Below are a series of examples illustrating the growth of highly luminescent nanostructures.
[0243] Example 1
[0255] We describe the deposition of thick ZnSe / ZnS multilayer shells on green InP cores using zinc oleate, tri-n-butylphosphine selenide, and octanethiol as precursors at temperatures above 280° C. The synthesis of green InP cores is disclosed in U.S. Patent Application Publication No. 2014 / 0001405.
[0244]
[0256] The stoichiometry of an InP core was calculated with an absorption peak at 470 nm, a concentration of 66.32 mg / mL in hexane, and shell thicknesses of 3.5 monolayers of ZnSe and 4.5 monolayers of ZnS. Zinc oleate was prepared as a solid from zinc acetate and oleic acid. TBPSe was prepared from selenium pellets and tri(n-butyl)phosphine.
[0245]
[0257] To a 250 mL 3-neck round bottom flask was added 3.48 g (5.54 mmol, 13.38 equiv.) zinc oleate and 33.54 mL 1-octadecene at room temperature in air. The flask was fitted with a stir bar, rubber septum, Schlenk adapter, and thermocouple. The flask was connected to a Schlenk line with a rubber hose. Inert conditions were established by at least three cycles of vacuum (<50 mtorr) and nitrogen flushing. The mixture was heated to 80° C. under a stream of nitrogen to give a clear solution. This temperature was maintained and the flask was again placed under vacuum and the pump was applied until no further gas evolution (<50 mtorr) was observed. The heating mantle was removed and the flask was cooled under a stream of nitrogen.
[0246]
[0258] When the temperature was about 50°C, 0.060 g (0.41 mmol, 1.00 equiv) of InP (core diameter = 17.79 Angstroms) in 0.91 mL of hexane was added. The flask was carefully placed under vacuum and the mixture was pumped to <50 mtorr to remove the hexane. The reaction mixture was then heated to 80°C under a stream of nitrogen to give a clear solution. 2.52 mL (5.04 mmol, 12.16 equiv) of tri-n-butylphosphine selenide (TBPSe) was added at about 100°C. The temperature was set to 280°C and a timer was started. A reaction temperature of 280°C was reached after about 16 minutes and then maintained until the timer counted 40 minutes. The heating mantle was removed and the flask was allowed to cool naturally.
[0247]
[0259] When the temperature was below 100°C, the nitrogen flow was increased to 15 standard cubic feet per hour, the septum was removed, and 16.57 g (26.38 mmol, 63.72 equiv.) zinc oleate and 0.45 g (2.25 mmol, 5.48 equiv.) lauric acid were added through the powder funnel. After reinserting the septum, the flask was carefully placed under vacuum until no further gas evolution (<50 mtorr) was observed. For etching of the buffer layer, the reaction mixture was heated to 280°C under nitrogen flow and maintained for 15 minutes (including heat-up time, timing began when the heater was started). The reaction flask was then allowed to cool naturally. 4.16 mL (23.98 mmol, 57.93 equiv.) octanethiol was added by syringe at approximately 130-150°C. The temperature was set to 300°C and the timer was started again. The reaction temperature was reached after approximately 14 minutes and maintained for 50 minutes. The heating mantle was removed and the flask was allowed to cool naturally.
[0248]
[0260] Once the temperature of the reaction mixture was below 100°C, the thermocouple was replaced with a glass stopper under a stream of nitrogen. The flask was carefully placed under a slight vacuum and placed in a glove box along with two PTFE bottles. The mixture was poured into one PTFE bottle, and the flask was rinsed twice with 4 mL of hexane, which was added to the PTFE bottle. The mixture in the bottle was cooled to room temperature and then centrifuged at 4000 rpm for 5 minutes to separate the insoluble material. The clear but colorful supernatant was decanted into a second PTFE bottle, and 16 mL of hexane was added to the first PTFE bottle to further extract the quantum dot material from the insoluble by-products. The first bottle was shaken and vortexed to ensure thorough mixing, and then centrifuged at 4000 rpm for 5 minutes. This supernatant was combined with the first supernatant in the second PTFE bottle, at which point the lighter insoluble wax in the first bottle was discarded. The combined supernatants were precipitated with ethanol (2 volumes, approximately 120 mL) and centrifuged at 4000 rpm for 5 min, at which point the nearly colorless supernatant was discarded and the centrifuged material was redispersed in a total of 4 mL toluene (first 2 mL, then two 1 mL rinses).
[0249]
[0261] During the reaction, aliquots of approximately 50 μL were taken approximately every 15 min for spectroscopic analysis. These aliquots were immediately quenched in 1 mL of hexane and then further diluted by adding approximately 100 μL of this sample to 4 mL of hexane in a cuvette. Absorbance, fluorescence, and fluorescence excitation (at peak emission wavelength) spectroscopy were performed on this cuvette.
[0250]
[0262] At the end of each step (ZnSe and ZnS shells), aliquots of approximately 200 μL were taken for TEM analysis. These were then washed three times with a 1:3 solution of hexane:ethanol in a glove box. OD 350 A solution of 0.4 in hexane is submitted for TEM analysis.
[0251]
[0263] For quantum yield (QY) measurements, 0.5 mL aliquots were taken from the combined supernatants during workup (or after the last reaction step during cooling) and submitted for quantum yield analysis.
[0252] Example 2
[0264] We describe the deposition of thick ZnSe / ZnS multilayer shells on green InP cores using zinc oleate, tri-n-butylphosphine selenide, and octanethiol as precursors at temperatures above 280° C. The resulting nanostructures had target shell thicknesses of 1.5 monolayers of ZnSe and 2.5 monolayers of ZnS.
[0253]
[0265] To a 100 mL 4-neck round bottom flask was added 0.409 g (0.651 mmol, 3.1 equiv.) zinc oleate and 2 mL 1-octadecene at room temperature in air. The flask was fitted with a glass stopper, rubber septum, Schlenk adapter, and thermocouple. The flask was connected to a Schlenk line with a rubber hose. Inert conditions were established by at least three cycles of vacuum (<50 mtorr) and nitrogen flushing. The mixture was heated to 80° C. under a stream of nitrogen to give a clear solution. This temperature was maintained and the flask was again placed under vacuum and the pump was applied until no further gas evolution (<50 mtorr) was observed. The heating mantle was removed and the flask was cooled under a stream of nitrogen.
[0254]
[0266] When the temperature was about 50° C., 0.030 g (0.21 mmol, 1.00 equiv.) of InP (core diameter=18.43 Å) in 0.46 mL of hexane was added. The flask was placed under vacuum and the hexane was removed using a pump to <50 mtorr. The reaction mixture was then heated to 80° C. under a stream of nitrogen to give a clear solution. 0.308 mL (0.616 mmol, 2.93 equiv.) of tri-n-butylphosphine selenide (TBPSe) was added at about 100° C. The temperature was set to 280° C. and a timer was started. A reaction temperature of 280° C. was reached after about 16 minutes and then maintained until the timer counted 40 minutes. The heating mantle was removed and the flask was allowed to cool naturally.
[0255]
[0267] When the temperature was below 100°C, the nitrogen flow was increased to 15 standard cubic feet per hour, the septum was removed, and 1.77 g (2.82 mmol, 13.41 equiv.) of zinc oleate was added through the powder funnel. After reinserting the septum, the flask was carefully placed under vacuum until no further gas evolution (<50 mtorr) was observed. The reaction mixture was heated to 280°C under nitrogen flow and maintained for 15 minutes (including heat-up time, timing began when the heater was started). The reaction flask was then allowed to cool naturally. 0.45 mL (2.59 mmol, 12.35 equiv.) of octanethiol was added via syringe at approximately 130-150°C. The temperature was set to 300°C and the timer was started again. The reaction temperature was reached after approximately 14 minutes and maintained for 50 minutes. The heating mantle was removed and the flask was allowed to cool naturally.
[0256]
[0268] Once the temperature of the reaction mixture was below 100°C, the thermocouple was replaced with a glass stopper under a stream of nitrogen. The flask was carefully placed under a slight vacuum and placed in a glove box along with two PTFE bottles. The mixture was poured into one PTFE bottle, and the flask was rinsed twice with 4 mL of hexane, which was added to the PTFE bottle. The mixture in the bottle was cooled to room temperature and then centrifuged at 4000 rpm for 5 minutes to separate the insoluble material. The clear but colorful supernatant was decanted into a second PTFE bottle, and 16 mL of hexane was added to the first PTFE bottle to further extract the quantum dot material from the insoluble by-products. The first bottle was shaken and vortexed to ensure thorough mixing, and then centrifuged at 4000 rpm for 5 minutes. This supernatant was combined with the first supernatant in the second PTFE bottle, at which point the lighter insoluble wax in the first bottle was discarded. The combined supernatants were precipitated with ethanol (2 volumes, approximately 120 mL) and centrifuged at 4000 rpm for 5 min, at which point the nearly colorless supernatant was discarded and the centrifuged material was redispersed in a total of 4 mL toluene (first 2 mL, then two 1 mL rinses).
[0257]
[0269] During the reaction, aliquots of approximately 50 μL were taken approximately every 15 min for spectroscopic analysis. These aliquots were immediately quenched in 1 mL of hexane and then further diluted by adding approximately 100 μL of this sample to 4 mL of hexane in a cuvette. Absorption, fluorescence, and fluorescence excitation (at peak emission wavelength) spectroscopy were then performed.
[0258]
[0270] At the end of each step (ZnSe and ZnS shells), an aliquot of approximately 200 μL was taken for TEM analysis, followed by washing three times with a 1:3 solution of hexane:ethanol in a glove box. 350 A solution of 0.4 in hexane is submitted for TEM analysis.
[0259]
[0271] For quantum yield (QY) measurements, 0.5 mL aliquots were taken from the combined supernatants during workup (or after the last reaction step during cooling) and submitted for quantum yield analysis.
[0260] Example 3
[0272] Using the synthesis method of Example 2, and varying the amount of zinc oleate and octanethiol added to the reaction mixture, nanostructures with green InP cores were fabricated with target shell thicknesses of 1.5 monolayers of ZnSe, (A) 4.5 monolayers of ZnS, and (B) 7.5 monolayers of ZnS. The following amounts of zinc oleate and octanethiol precursors were used to form the ZnS shell: (A) For 4.5 monolayers of ZnS: 4.47 g zinc oleate; and 1.13 mL of octanethiol. (B) For 7.5 monolayers of ZnS: 11.44 g zinc oleate; and 2.88 mL of octanethiol.
[0261] Example 4
[0273] Using the synthesis method of Example 2, and varying the amounts of zinc oleate, TOPSe, and octanethiol added to the reaction mixture, nanostructures with green InP cores were fabricated with target shell thicknesses of 2.5 monolayers of ZnSe and (A) 2.5 monolayers of ZnS, (B) 4.5 monolayers of ZnS, and (C) 7.5 monolayers of ZnS. The following amounts of zinc oleate and TOPSe precursors were used to form the ZnSe shells of all three nanostructures: 0.90 g zinc oleate; and 0.68 mL (1.92 M TOPSe). To form the ZnS shell, the following amounts of zinc oleate and octanethiol precursors were used: (A) 2.5 monolayers of ZnS (~50.33 Å for nanostructures): 2.47g zinc oleate; 0.62mL of octanethiol. (B) 4.5 monolayers of ZnS (~62.73 Å for nanostructures): 6.91 g zinc oleate; and 1.49 mL of octanethiol. (C) 7.5 monolayers of ZnS (~81.33 Å for nanostructures): 15.34 g zinc oleate; and 3.61 mL of octanethiol.
[0262] Example 5
[0274] Using the synthesis method of Example 2, nanostructures with green InP cores were fabricated with target shell thicknesses of 3.5 monolayers of ZnSe, (A) 4.5 monolayers of ZnS, and (B) 7.5 monolayers of ZnS, by varying the amounts of zinc oleate, TBPSe, and octanethiol added to the reaction mixture. The following amounts of zinc oleate and TBPSe precursors were used to form the ZnSe shells of all three nanostructures: 0.97 g zinc oleate; and 0.70 mL (2 M TBPSe). To form the ZnS shell, the following amounts of zinc oleate and octanethiol precursors were used: (A) 4.5 monolayers of ZnS (~69.29 Å for nanostructures): 4.55 g zinc oleate; and 1.14 mL of octanethiol. (B) 7.5 monolayers of ZnS (~87.89 Å for nanostructures): 10.56 g zinc oleate; and 2.65mL of octanethiol.
[0263] Example 6
[0275] Nanostructures using a red InP core (core diameter=27.24 Å, 0.0581 g InP) with 3.5 monolayers of ZnSe and 4.5 monolayers of ZnS were fabricated using the synthesis method of Example 2 by varying the amounts of zinc oleate, TBPSe, and octanethiol added to the reaction mixture. The following amounts of zinc oleate and TBPSe precursors were used to form the ZnSe shell: 1.60% zinc oleate; and 1.16mL (2M TBPSe). Zinc oleate and octanethiol precursors were used to form the ZnS shell (approximately 78.10 Å for the nanostructures). 6.08 g zinc oleate; and 1.53mL of octanethiol.
[0264] Example 7
[0276] The procedure involves the growth of thick ZnSe on green InP cores using zinc oleate, tri-n-butylphosphine selenide (TBPSe), and octanethiol as precursors at temperatures above 280 °C. x S 1-x The deposition of a ZnS shell is described.
[0265]
[0277] Absorption peak at 479 nm, concentration of 59.96 mg / mL in hexane, and 3.5 monolayers of ZnSe x S 1-x The stoichiometry of an InP core with (x=0.5) and a shell thickness of 4.5 monolayers of ZnS was calculated. Zinc oleate was prepared as a solid from zinc acetate and oleic acid. TBPSe was prepared as a 2 M solution from selenium pellets and tri(n-butyl)phosphine.
[0266]
[0278] To a 250 mL 3-neck round bottom flask were added 17.8 g (28.34 mmol, 69.12 equiv.) zinc oleate, 5.68 g (28.34 mmol) lauric acid, and 33 mL 1-octadecene at room temperature in air. The flask was fitted with a stir bar, rubber septum, Schlenk adapter, and thermocouple. The flask was connected to a Schlenk line with a rubber hose. Inert conditions were established by at least three cycles of vacuum (<80 mtorr) and nitrogen flushing. The mixture was heated to 80° C. under a stream of nitrogen to give a clear solution. The heating mantle was removed and the flask was cooled under a stream of nitrogen.
[0267]
[0279] When the temperature was approximately 100°C, 0.060 g (0.41 mmol, 1.00 equiv.) InP in 0.41 mL hexane was added. The flask was placed under vacuum and the mixture was pumped to <80 mtorr to remove the hexane for 10 minutes. The temperature was set to 280°C under a stream of nitrogen. When the temperature was approximately 100°C, 1.26 mL (2.53 mmol, 6.17 equiv.) tri-n-butylphosphine selenide (TBPSe) and 0.44 mL (2.53 mmol, 6.17 equiv.) octanethiol were added. A timer was started. A reaction temperature of 280°C was reached after approximately 16 minutes and then maintained until the timer counted to 80 minutes. The temperature was then set to 310°C. 4.04 mL (23.29 mmol, 56.80 equiv.) octanethiol was added dropwise over 20 minutes via syringe pump. After all the octanethiol had been added, the temperature was maintained at 310° C. for 60 minutes. The heating mantle was removed and the flask was allowed to cool naturally.
[0268]
[0280] Once the temperature of the reaction mixture was below 120°C, the thermocouple was replaced with a glass stopper under a stream of nitrogen. The flask was carefully placed under a slight vacuum and placed in a glove box along with one PTFE bottle. The mixture was poured into the PTFE bottle and the flask was rinsed twice with 4 mL of hexane and the washings were added to the PTFE bottle. The mixture in the bottle was cooled to room temperature and then centrifuged at 4000 rpm for 5 minutes to separate the insoluble material. The mixture was allowed to sit overnight. The clear but colorful supernatant was decanted into a second PTFE bottle and 16-20 mL of hexane was added to the first PTFE bottle to further extract the quantum dot material from the insoluble by-products. The first bottle was shaken and vortexed to ensure thorough mixing and then centrifuged at 4000 rpm for 5 minutes. This supernatant was combined with the first supernatant in the second PTFE bottle, at which point the lighter insoluble wax in the first bottle was discarded. The combined supernatants were precipitated with ethanol (2.5 volumes) and centrifuged at 4000 rpm for 5 min. At this point the nearly colorless supernatant was discarded and the centrifuged material was redispersed in a total of 20 mL of hexane. The bottle was allowed to sit for approximately 15 min to allow further solids to settle. If solids had settled, the bottle was centrifuged at 4000 rpm for 5 min. The clear solution was transferred to another bottle. This solution was washed with 2.5 volumes of ethanol (50 mL) to precipitate the QDs. The slightly milky supernatant was decanted. 3-4 mL of toluene was added to redisperse the QDs. The bottle was rinsed with 2 × 1 mL of toluene.
[0269]
[0281] During the reaction, aliquots of approximately 50 μL were taken approximately every 15 min for spectroscopic analysis. These aliquots were immediately quenched in 1 mL of hexane and then further diluted by adding approximately 100 μL of this sample to 4 mL of hexane in a cuvette. Absorbance, fluorescence, and fluorescence excitation (at peak emission wavelength) spectroscopy were performed on this cuvette.
[0270]
[0282] At the end of each step (ZnSe and ZnS shells), aliquots of approximately 200 μL were taken for TEM analysis. These were then washed three times with a 1:3 solution of hexane:ethanol in a glove box. OD 350 A solution of 0.4 in hexane is submitted for TEM analysis.
[0271]
[0283] For quantum yield (QY) measurements, 0.5 mL aliquots were taken from the combined supernatants during workup (or after the last reaction step during cooling) and submitted for quantum yield analysis.
[0272] Example 8
[0273] [Table 1]
[0274]
[0284] Using TBPSe instead of TOPSe as the selenium source increased the red shift and increased the quantum yield, as shown in Table 1. Furthermore, concentrating the InP core increased the red shift and increased the quantum yield, as shown in Table 1.
[0275] Example 9
[0285] Using the synthesis method of Example 2, nanostructures with green InP cores (457 nm absorption peak, 58 mg InP) were fabricated with various target shell thicknesses of 2.0 or 2.5 monolayers of ZnS and (A) 2.5 monolayers, (B) 3.5 monolayers, (C) 4.0 monolayers, and (D) 4.0 monolayers of ZnSe by varying the amounts of zinc oleate, TBPSe, and octanethiol added to the reaction mixture.
[0276]
[0286] To form a ZnSe / ZnS shell with 2.5 monolayers of ZnSe and 2.0 monolayers of ZnS, the following amounts of zinc oleate, TBPSe, and octanethiol precursor were used: 10.3g zinc oleate; 0.73 mL of TBPSe (4M); and 1.06 mL of octanethiol.
[0277]
[0287] To form a ZnSe / ZnS shell with 3.5 monolayers of ZnSe and 2.5 monolayers of ZnS, the following amounts of zinc oleate, TBPSe, and octanethiol precursor were used: 10.3g zinc oleate; 1.32 mL of TBPSe (4M); and 1.93mL of octanethiol.
[0278]
[0288] To form a ZnSe / ZnS shell with 4.0 monolayers of ZnSe and 2.5 monolayers of ZnS, the following amounts of zinc oleate, TBPSe, and octanethiol precursor were used: 12.3g zinc oleate; 1.71 mL of TBPSe (4M); and 2.20 mL of octanethiol.
[0279]
[0289] To form a ZnSe / ZnS shell with 4.5 monolayers of ZnSe and 2.0 monolayers of ZnS, the following amounts of zinc oleate, TBPSe, and octanethiol precursor were used: 12.2g zinc oleate; 2.15 mL of TBPSe (4M); and 1.88mL of octanethiol.
[0280] Example 10
[0290] The optical properties of the nanostructures produced in Example 9 were analyzed, as shown in Table 2.
[0281] [Table 2]
[0282]
[0291] The increased blue light normalized absorption is measured as the ratio of the optical density at 450 nm to the optical density at the first exciton peak absorption wavelength. The exciton peak is solely due to absorption by the InP core, while the higher energy absorption at wavelengths below 460 nm comes from photon absorption in the ZnSe shell and increases with shell volume. This also means that the optical density per particle increases by 82% when going from, for example, a 2.5 monolayer (ML) to a 4.5 ML ZnSe shell. Due to absorption in the shell, the high energy shell excitons are rapidly transferred to the core, where emission occurs due to the excited state. This transfer is not quantitative, as indicated by the lower quantum yield of the thicker shell material, but the increase in absorption is relatively larger than the decrease in quantum yield, so more blue photons are converted to green photons by these thicker shell materials.
[0283]
[0292] Figure 10 shows the absorption spectra of samples with increasing ZnSe shell thickness. These spectra are normalized by the exciton peak. Thus, the increased shell absorption can be clearly seen from the absorption intensity at 450 nm.
[0284] Example 11
[0293] Another way to increase the absorbance is to decrease the shell band gap. A green InP core (absorption peak at 457 nm, 58 mg of InP) with 3.5 monolayers of ZnSe 0.975 Te 0.025 Nanostructures with target shell thicknesses of 2.5 monolayers of ZnS were fabricated using the synthesis method of Example 2 with the following amounts of zinc oleate, TBPSe, trioctylphosphine telluride (prepared by dissolving elemental tellurium in trioctylphosphine), and octanethiol precursor added to the reaction mixture: 10.3g zinc oleate; 1.32 mL of TBPSe (4M); 0.66 mL of TOPTe (0.2 M); and 1.93mL of octanethiol.
[0285]
[0294] FIG. 11 shows an example with 2.5 mol% tellurium alloyed in the ZnSe shell compared to a Te-free sample at the same peak wavelength. 450 The peak / peak ratio clearly increases further.
[0286] Example 12
[0295] InP / ZnSe / ZnS red quantum dots were fabricated as described in Example 2. The relative precursor amounts of zinc oleate, trioctylphosphine selenide (TOPSe), and dodecanethiol (DDT) were varied to control the shell thickness. For example, to increase the ZnSe layer thickness from 2.5 to 4.5 monolayers, the amount of TOPSe was increased by a factor of 1.7. After fabricating a series of resulting quantum dots with various shell thicknesses, quantum dot LEDs can then be fabricated.
[0287] Example 13
[0296] The device was fabricated by a combination of spin-coating and thermal evaporation. First, the hole-injecting material poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) (50 nm) was spin-coated onto a UV-ozone-treated indium tin oxide (ITO) substrate and baked at 200 °C for 15 min. The device was transferred to an inert atmosphere, and the hole-transporting material poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))] (TFB) (18 nm) was deposited by spin-coating and baked at 135 °C for 15 min. QD-1 (2.5 nanometers) prepared by the method of Example 12 was used. A solution of either QD-1 (InP quantum dots with 4.5 monolayers of ZnSe and 4.5 monolayers of ZnS) or QD-2 (InP quantum dots with 4.5 monolayers of ZnSe and 3 monolayers of ZnS) was deposited by spin coating, followed by spin coating of the electron transport material ZnMgO (60 nm). An Al cathode (150 nm) was then deposited by thermal evaporation, followed by encapsulation of the device with a cap glass, getter, and epoxy resin.
[0288]
[0297] The device with the emissive layer composed of QD-2, shown in Figure 12, exhibited a higher maximum external quantum efficiency (EQE) than the device with the emissive layer composed of QD-1 (EQE of 8.0% vs. 6.0%, respectively). The device with the QD-2 emissive layer also exhibited higher luminance at 7 V than the device with the emissive layer composed of QD-2 (4000 cd / m, respectively). 2 2800cd / m 2 ) Both devices exhibit similar current densities over a range of voltages, indicating that the thicker shell of QD-2 does not significantly impede changer injection or transport.
[0289]
[0298] Samples with the following configurations were also tested: Device-1 (glass / TFB(20 nm) / QD-1(20 nm) / ZnMgO(60 nm)) and Device-2 (glass / TFB(20 nm) / QD-2(20 nm) / ZnMgO(60 nm)). As shown in FIG. 13, QD-1 and QD-2 showed similar solution-state quantum yields (86% vs. 89%, respectively), but the partial device containing QD-2 showed significantly more solid-state quantum yield than QD-1 (27% vs. 36%, respectively). This is believed to be a result of the increased shell thickness, which increases the confinement of electrons and holes. By increasing the spacing between the cores, the thicker shell also reduces the probability of nonradiative pathways associated with energy transfer between quantum dots.
[0290]
[0299] It is believed that increasing the ZnSe / ZnS thickness will continue to improve the device EQE until a trade-off with charge injection or strain due to lattice mismatch is reached. Since both shell thickness and ligand length and composition affect charge injection and confinement, modifying the ligand composition at the new optimized shell thickness will further improve the EQE. The synthesis techniques used to control the shell thickness can also be used to modify the shell ZnSe / ZnS composition. The resulting ZnSe / ZnS gradient can also be used to improve the solid-state quantum yield, resulting in a higher device EQE.
[0291] Example 14
[0300] Nanostructures using an InP core (core diameter = 27.24 Angstroms, 0.0581 g InP) with 10.5 monolayers of ZnSe and 3 monolayers of ZnS were fabricated using the synthesis method of Example 2 by varying the amounts of zinc oleate, TBPSe, and octanethiol added to the reaction mixture. The following amounts of zinc oleate and TBPSe were used to form the ZnSe shell: 13.01 g zinc oleate; and 9.41mL of 2M TBPSe. To form the ZnS shell, the following amounts of zinc oleate and octanethiol precursors were used: 10.76 g zinc oleate; and 2.70 mL of octanethiol.
[0292]
[0301] Having thus fully described the invention, it will be understood by those skilled in the art that the same may be practiced within a wide equivalent range of conditions, formulations, and other parameters without affecting the scope of the invention or any of its embodiments. All patents, patent applications, and publications cited herein are hereby incorporated by reference in their entirety.
Claims
1. 1. A nanostructured shaped article comprising: (a) a first barrier layer; (b) a second barrier layer; (c) a nanostructured layer between the first barrier layer and the second barrier layer, wherein the nanostructure is a multilayer nanostructure comprising an InP / ZnSe / ZnS core / shell nanostructure, the ZnSe shell comprising 2.5 monolayers or more and the ZnS shell comprising 3 monolayers or more, and wherein the nanostructure has a normalized optical density at 450 nm between 1.0 and 3.
0.
2. The nanostructured molded article of claim 1 further comprising a hole injection material.
3. 10. The nanostructured molded article of claim 1, further comprising a hole injection material comprising poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate).
4. The nanostructured molded article of claim 1 further comprising a hole transport material.
5. 10. The nanostructured molded article of claim 1, further comprising a hole transport material comprising poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))].
6. The nanostructured molded article of claim 1 further comprising an electron transport material.
7. 10. The nanostructured molded article of claim 1, further comprising an electron transport material comprising ZnMgO.
8. 10. The nanostructured molded article of claim 1, wherein the molded article exhibits an external quantum efficiency (EQE) of between 6% and 20%.
9. The molded article has a resolution of 3000 cd / m at 7 volts. 2 ~6000cd / m 2 13. The nanostructured molded article of claim 1, having a brightness between 0.1 and 0.25.
Citation Information
Patent Citations
Quantum dot luminous device, fabrication method thereof and display device
CN106206967A
Quantum dot electroluminescent device, preparation method thereof and display device
CN106229423A
High-brightness nanostructures and methods for producing them
JP2015529698A
Semiconductor nanocrystal, and method of preparing the same
US20140117292A1
Low Cadmium Content Nanostructure Compositions and Uses Thereof
US20170250322A1